Method for recovering lithium and other metals from waste lithium-ion batteries

The method uses a polar solvent with alkaline earth hydroxides to leach lithium salts and separate transition metals from lithium-ion battery materials, improving purity and reducing energy consumption in the recovery process.

JP7617077B2Active Publication Date: 2025-01-17BASF SE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022504519
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-14
Filing Date
2020-07-24
Publication Date
2025-01-17
Estimated Expiration
2040-07-24

AI Technical Summary

Technical Problem

Existing methods for recovering valuable metals from lithium-ion batteries are complex, require multiple energy-intensive steps, and struggle with the removal of impurities such as fluorine and phosphorus compounds, leading to low purity of recovered materials.

Method used

A method involving the use of a polar solvent, typically an aqueous solvent with an alkaline earth hydroxide, to leach lithium salts from particulate materials derived from lithium-ion batteries, followed by solid-liquid and optional solid-solid separations to isolate transition metals like nickel and cobalt, and subsequent smelting to obtain metal melts.

Benefits of technology

This approach allows for the efficient recovery of high-purity lithium hydroxide and transition metals with reduced energy consumption and fewer process steps, effectively addressing the impurity challenges of previous methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617077000007
    Figure 0007617077000007
  • Figure 0007617077000008
    Figure 0007617077000008
  • Figure 0007617077000009
    Figure 0007617077000009
Patent Text Reader

Abstract

A method for recovering one or more transition metals and lithium from waste lithium-ion batteries or parts thereof is disclosed. The method includes the steps of: (a) preparing a particulate material containing a transition metal compound and / or a transition metal, where the transition metal is selected from the group consisting of Ni and Co, and further, if present, at least a portion of the Ni and / or Co is in an oxidation state lower than +2, e.g., metallic, and the particulate material further contains a lithium salt; (b) treating the material prepared in step (a) with a polar solvent and, optionally, an alkaline earth hydroxide; (c) separating the solid from the liquid, optionally followed by solid-solid separation; and (d) treating the transition metal-containing solid in a smelting furnace to obtain a metal melt containing Ni and / or Co. The method provides good separation of the transition metal as an alloy and high-purity lithium.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is directed to a method for recovering lithium and other metals from spent lithium-ion batteries or production waste containing at least one of the transition metals nickel, manganese and cobalt, in particular a method that concerns the extraction of lithium as lithium hydroxide from particulate material obtained from lithium-ion batteries, in particular their cell materials, typically after discharge, crushing and reduction at high temperatures, and the separation of lithium from undesired impurities in a refining process by recovering other metals, such as nickel, manganese and / or cobalt, from the residue after the extraction step. [Background technology]

[0002] The storage of electrical energy is a subject of growing interest. Efficient storage of electrical energy allows for the generation of electrical energy when and where it is needed. Secondary lithium batteries are of particular interest for energy storage because, due to the small atomic weight and large ionization energy of lithium, they provide high energy density and have become widely used as power sources for many portable electronic devices, such as mobile phones, laptop computers, mini cameras, etc., as well as for electric vehicles. In particular, the increasing demand for raw materials, such as lithium, cobalt, and nickel, will create challenges in the future.

[0003] The life span of lithium-ion batteries is not unlimited. Therefore, it is expected that an increasing number of used lithium-ion batteries will be generated. Since lithium-ion batteries contain important transition metals, such as but not limited to cobalt and nickel, as well as lithium, used lithium-ion batteries may form a valuable source of raw materials for the new manufacture of lithium-ion batteries. For this reason, an increasing number of research activities are being carried out with the goal of recycling transition metals and lithium from second-hand lithium-ion batteries or from batteries or parts thereof that do not meet specifications and requirements (such off-specification materials and production waste may also be a source of raw materials).

[0004] Two main processes are the subject of raw material recovery. One main process is the direct hydrometallurgical process of battery scrap materials. The principle is disclosed in WO 2017 / 091562 and J. Power Sources, 2014, 262, 255 ff. Such hydrometallurgical processes will provide transition metals as aqueous solutions, for example as sulfate solutions, or in precipitated form, for example as hydroxides, separately or already with the stoichiometries desired for making new cathode active materials. In the latter case, the composition of the metal salt solution may be adjusted to the desired stoichiometry by adding single metal components.

[0005] WO 2017 / 091562 describes the co-precipitation of transition metals. WO 2014 / 180743 describes a co-precipitation process using ammonia or amines.

[0006] Typically, the batteries are first disassembled into modules or even into cells. In the case of direct hydrometallurgical processes, the battery scrap is mechanically processed to separate larger parts from the casing and wiring. The electrode active material, i.e. graphite in the case of the anode and lithium transition metal oxide in the case of the cathode, together with some impurities, forms a fine powder, the so-called black mass or black powder, which constitutes the feed for the subsequent hydrometallurgical process steps. In some processes, the battery scrap is subjected to a heat treatment or pyrolysis step carried out at a temperature well below the melting point of the transition metals contained in the scrap, in this respect differing from the refining process, which operates at a temperature above the melting point of the transition metals contained in the scrap.

[0007] Such heat-treated black mass can result from the treatment of batteries in a waste incineration oven. Waste batteries, or battery modules or cells, are fed to the incineration oven, where the battery feed is partially combusted. The products of this treatment are cooled and mechanically treated using any type of crushing or grinding equipment suitable for separating the metal fraction from the powdery black mass. These black masses are low reactive materials under normal conditions and can therefore be easily transported.

[0008] Heat treatment at high temperatures above 400 °C of spent lithium-ion batteries or parts containing the electrode active materials of these types of batteries has been described by several authors. Such heat treatment completely evaporates the electrolyte solvent contained by the battery and decomposes the polymer components. The material resulting from such heat treatment may be subjected to different mechanical treatments and separation operations in order to separate the different metal fractions and powder materials, mainly comprising the electrode active materials from the anode, i.e. graphite, and the electrode active materials from the cathode, i.e. lithium-containing transition metal materials. These powders are often called "black masses" or "black powders", or "active masses". Depending on the reaction conditions, the latter materials are often at least partially reduced, thereby containing metallic Ni and Co phases, manganese oxide phases, and lithium salts such as LiOH, Li2CO3, LiF, LiAlO2, Li3PO4. The reduction occurs either by the introduction of reducing gases such as hydrogen or carbon monoxide during the heat treatment, or by the carbonaceous materials contained in the waste battery material, i.e. graphite and soot, at temperatures above 500° C. J. Li et al., J. Hazard. Mat. 2016, 302, 97 ff. discloses an oxygen-free roasting / wet magnetic separation process for the reclamation of cobalt, lithium carbonate and graphite from spent LiCoO2 / graphite batteries.

[0009] In JP2012-229481, waste batteries are treated in multiple steps in a way that binds the fluorine they contain in a conductive electrolyte salt, usually LiPF6, and a binder polymer, usually polyvinylidene fluoride (PVDF). This is achieved by first treating the waste batteries with an aqueous calcium hydroxide (slaked lime) solution to hydrolyze the conductive salt and precipitate the fluoride as calcium fluoride. Starting from conversion experiments with model substances such as LiCoO2, JP2012-229481 discloses a method for recovering metals from used lithium-ion batteries, including a pre-soaking step, followed by aqueous treatment with high-temperature oxidation, reduction roasting, filtration, and recovery of lithium carbonate from the filtrate and transition metals from the residue.

[0010] The other main method is based on the direct smelting of the corresponding battery scrap (for example EP 1 589 121 A1). This results in a metal alloy containing Ni and Co, while lithium is lost in the slag from which it is very difficult to recover. The obtained metal alloy can be processed by hydrometallurgy to extract metals, such as transition metals. JP 2012-112027 A describes the separation of lithium and cobalt by evaporation from the melt, and therefore such a method is envisaged to operate above the boiling temperature of cobalt (i.e. above 2870° C.). Valuable metals [Prior art documents] [Patent documents]

[0011] [Patent Document 1] International Publication No. 2017 / 091562 [Patent Document 2] International Publication No. 2014 / 180743 [Patent Document 3] JP 2012-229481 A [Patent Document 4] European Patent Application Publication No. 1589121 [Patent Document 5] JP 2012-112027 A [Non-patent literature]

[0012] [Non-Patent Document 1] J. Power Sources, 2014, 262, 255 ff. [Non-Patent Document 2] J. Li et al., J. Hazard. Mat. 2016, 302, 97 ff Summary of the Invention [Problem to be solved by the invention]

[0013] Known methods of recovering valuable materials typically face the problem that used batteries, i.e. the cells in which they are and contain the majority of these materials, contain high levels of impurities such as fluorine and / or phosphorus compounds, which must be removed in order to recover the desired materials (battery grade materials) in a purity that can be used for the production of new cells. It is therefore an object of the present invention to provide a method that allows easy recovery of the valuable metals contained in battery scrap, i.e. lithium, nickel and, if present, cobalt and manganese. It is another object of the present invention to provide a method to recover further elements, e.g. carbon as graphite and fluorides. It is a further object of the present invention to provide an economical method that reduces the number of expensive and / or energy consuming steps. It is a further object of the present invention to provide a method to recover the transition metals or compounds thereof in high purity, in particular with low contents of copper and precious metals such as Ag, Au and platinum group metals, as well as high purity lithium or compounds thereof with low contents of fluorine and / or phosphorus, or other metallic impurities. Typically, the recovered metals or metal compounds are converted to the corresponding transition metal salts, often sulfates, and lithium carbonate and often lithium hydroxide.

[0014] Known methods for binding fluoride are typically complex and require multiple process steps. It is therefore an object of the present invention to solve the above-mentioned problems of recovering Ni, Co and lithium hydroxide from at least partially reduced black masses containing Ni and / or Co, at least 10% of which is present in an oxidation state lower than +2, e.g., metallic state, and also containing lithium salts. Such black masses are often ferromagnetic. [Means for solving the problem]

[0015] Thus, a method as defined at the outset has been found, hereinafter also referred to as the inventive method or the inventive recycling method, which comprises the steps defined in more detail below, hereinafter also referred to as step (a), step (b), step (c), step (d) etc.

[0016] The present invention therefore primarily relates to a method for recovering one or more transition metals and lithium, as Li salts, from materials comprising waste lithium ion batteries or parts thereof, comprising the steps of: (a) providing a particulate material obtained from a lithium ion battery or part thereof, the particulate material comprising a transition metal compound and / or a transition metal selected from the group consisting of Ni and Co, and further comprising at least a portion of the Ni and / or Co in an oxidation state lower than +2, the particulate material further comprising a lithium salt; (b) treating the material provided in step (a) with a polar solvent, typically an aqueous solvent; (c) separating the solid containing one or more transition metals from the liquid, optionally followed by subjecting the solid to solid-solid separation to recover the transition metal, e.g. Ni; and (d) treating the solid, and optionally a transition metal concentrate from the solid-solid separation, containing a majority of one or more transition metals, in a smelting furnace to obtain a metal melt containing Ni and / or Co. The present invention relates to a method comprising the steps of: [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is an X-ray powder diffraction pattern (Mo Ka) of reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1 and used in Example 2a, including reference diffractograms of graphite, cobalt, manganese-II oxide, cobalt oxide, and nickel. [Diagram 2] FIG. 2 is an X-ray powder diffraction pattern (Mo Ka) of the reduced mass from the spent lithium ion battery after heating / reduction treatment obtained in Example 1 and used in Example 2a, including reference diffraction patterns of graphite, lithium aluminate, and lithium carbonate. [Diagram 3] FIG. 2 is an X-ray powder diffraction pattern (Cu Ka) of the reduced mass from spent lithium ion batteries after heating / reduction treatment obtained in Example 1 and used in Example 2a, including reference diffraction patterns of graphite, cobalt, manganese-II oxide, cobalt oxide, and nickel. [Figure 4] FIG. 2 is an X-ray powder diffraction pattern (Cu Ka) of the reduced mass from the spent lithium ion battery after heating / reduction treatment obtained in Example 1 and used in Example 2a, including reference diffraction patterns of graphite, lithium aluminate and lithium carbonate. [Diagram 5] FIG. 1 is an X-ray powder diffraction pattern (Cu Ka) of LiOH monohydrate obtained in Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The particulate material prepared in step (a) is obtained from lithium-containing transition metal oxide material, which may typically originate from lithium-ion batteries (battery waste), including used batteries, waste battery materials and off-spec materials from production, which contain fluorine compounds and / or phosphorus compounds as impurities, as well as further materials containing lithium and said transition metals free of such impurities, such as cathode active materials from production waste. As described in more detail below for preliminary step (i), prior to this step (a), the material is subjected to a reduction step, for example using a reducing gas, such as CO or hydrogen, to convert the transition metals Ni and / or Co to an oxidation state lower than +2 or to a metallic state, for example by heating the material to a temperature in the range of 200-900° C. in the presence of H2.

[0019] As mentioned above, the solid residue separated in step (c) may be further subjected to solid-solid separation to recover the transition metal, e.g. Ni, prior to carrying out the present step (d), in which case the polar solvent used in step (b) contains an alkaline earth hydroxide.

[0020] The solid-liquid separation of step (c) may be followed by an optional solid-solid separation, or the slurry obtained from step (b) is subjected to a solid-solid separation and the resulting fraction is subsequently subjected to a solid-liquid separation. The optional solid-solid separation (described in more detail further below as step d1) produces a solid residue enriched in transition metals, in particular nickel and / or cobalt, and a second solid residue depleted in transition metals. The method offers the advantage of keeping the lithium salts in a form that allows recovery from solution, thus providing good recovery of lithium and transition metals.

[0021] The polar solvent used in step (b) of the method leaches the lithium salt from the material prepared in step (a), thereby providing the desired separation of lithium in the liquid phase from the transition metal remaining in the solid residue. The polar solvent is typically selected from water, alcohols, ketones, esters, organic carbonates, polyethers, nitriles and mixtures thereof. Particularly preferred are polar solvents that can at least partially dissolve alkaline earth hydroxides, such as calcium hydroxide, for example, as well as water, or even better. Examples of such solvents are polyols, such as glycols, glycerol or polyethylene glycols, and mixtures thereof.

[0022] To improve the leaching results for the recovery of lithium hydroxide, an alkaline earth hydroxide or alkaline earth oxide may be added to the slurry, and in the case of an alkaline earth oxide, such as calcium oxide, the polar solvent used in step (b) is advantageously a protic solvent which forms the alkaline earth hydroxide in situ, such as water.

[0023] In a process of particular technical importance, the leach liquid used in step (b) for treating the particulate material (PM) prepared in step (a) contains an alkaline earth hydroxide (AEH), for example calcium hydroxide. The addition of an alkaline earth hydroxide in this step has the advantage of binding with fluoride and other anions capable of forming less soluble lithium salts such as carbonates, phosphates, aluminates, further improving slagging and simplifying the separation of the metal or metal alloy from the product obtained in step (d).

[0024] Therefore, the present invention preferably relates to a method for recovering one or more transition metals and lithium as Li-salts from materials comprising waste lithium-ion batteries or parts thereof, comprising the steps of: (a) providing a particulate material obtained from waste lithium ion batteries or parts thereof, the particulate material comprising a transition metal compound and / or a transition metal selected from the group consisting of Ni and Co, wherein at least a portion of the Ni and / or Co is in an oxidation state lower than +2, the particulate material further comprising a lithium salt; (b) treating the material provided in step (a) with a polar solvent, typically an aqueous solvent, and an alkaline earth hydroxide; (c) separating the solid containing one or more transition metals from the liquid, optionally followed by subjecting the solid to solid-solid separation to recover the transition metal, e.g. Ni; and (d) treating said solid containing one or more transition metals, optionally a transition metal concentrate from the solid-solid separation, containing the majority of the transition metals, in a smelting furnace to obtain a metal melt containing Ni and / or Co. The present invention relates to a method, including

[0025] The PM preferably contains nickel and optionally a further transition metal, such as Co.

[0026] Protic solvents are primarily water, alcohols and mixtures thereof, as detailed below. An aqueous medium, e.g., an aqueous solvent or liquid, contains primarily (i.e., 50% by weight (% bw) or more, particularly 80% by weight or more, more particularly 90% by weight or more) water, including water and mixtures of water and one or more alcohols, and may contain additional dissolved substances, so long as the water content, which is critical, is maintained within one or more of the ranges given above.

[0027] Step (b) primarily involves providing a suspension of particulate material in a polar solvent, preferably carried out with heating, the treatment with alkaline earth hydroxide typically being carried out at temperatures in the range of 60-200°C, preferably 70-150°C. Above the boiling point of the polar solvent, the treatment is carried out in the liquid state, under pressure at which the solvent or at least a part of it is maintained. The temperature range around the boiling point of water, i.e. about 70-150°C, is of particular technical importance, in which case the treatment can be achieved at normal pressure or slightly higher pressures (e.g. up to 5 bar) using aqueous liquids or water. Alternatively, this step (b) can also be carried out by application of higher temperatures and pressures, e.g. 150-300°C and 1.5-100 bar.

[0028] The treatment is typically carried out by combining a quantity of alkaline earth hydroxide (AEH) with the particulate material (PM) corresponding to at least 5% of its weight, typically not more than 100%, e.g., 50-1000g AEH per kg PM, preferably 100-1000g AEH, more preferably 200-1000g AEH per kg PM. The amount of polar solvent is typically selected to ensure miscibility of the components, e.g., 0.5-95, preferably about 2.5-21 parts by weight of polar solvent, or in certain cases 1-20, e.g. about 2-10 parts by weight of polar solvent per part by weight of combined solids (PM and AEH).

[0029] In one embodiment of the present invention, step (b) is carried out in a container protected against strong bases, such as molybdenum and copper-rich steel alloys, nickel-based alloys, duplex stainless steel, or glass-lined or enamel- or titanium-coated steel. Further examples are polymer linings and containers made of base-resistant polymers, such as polyethylene, e.g., HDPE and UHMPE, fluorinated polyethylene, perfluoroalkoxyalkanes ("PFA"), polytetrafluoroethylene ("PTFE"), PVdF, and FEP. FEP stands for fluorinated ethylene propylene polymer, i.e., a copolymer of tetrafluoroethylene and hexafluoropropylene.

[0030] The treatment is typically carried out using a mixing device, such as a stirrer, typically applying a power of up to 10 W per kg of suspension, for example 0.5-10 W / kg, and / or circulating with a pump, in order to achieve good mixing and to avoid settling of insoluble components. The shear can be further improved by utilizing baffles. Furthermore, the slurry obtained in step (b) may advantageously be subjected to a grinding treatment, for example in a ball mill or a stirred ball mill, which allows better access of the polar solvent to the finely divided lithium-containing transition metal oxide material. The applied shear and grinding device is typically sufficiently corrosion resistant and can be produced from similar materials and coatings as those mentioned above for the vessel.

[0031] In one embodiment of the present invention, step (b) has a duration in the range of 20 minutes to 24 hours, preferably 1 to 10 hours.

[0032] In one embodiment, step (b) is carried out at least twice, with a solid-liquid separation between each run, until optimal recovery of lithium hydroxide or lithium salt is reached. The resulting lithium salt solutions may be combined or processed separately to recover the solid lithium salt.

[0033] In one embodiment of the invention, steps (b) and (c) are carried out in batch mode. In one embodiment of the invention, steps (b) and (c) are carried out in continuous mode, for example in a cascade of stirred vessels (step b) and / or in a cascade of stirred vessels plus a centrifuge (step c).

[0034] In one embodiment of the present invention, the polar solvent in step (b) is an aqueous medium, and the weight ratio of the aqueous medium to the material prepared in step (a) is in the range of 1:1 to 99:1, preferably 5:1 to 20:1.

[0035] The alkaline earth hydroxide is generally selected from hydroxides of Mg, Ca, Sr and Ba, with calcium hydroxide, barium hydroxide and mixtures thereof being preferred, with calcium hydroxide being most preferred. The alkaline earth hydroxide used in this step (b) may be used as such or may be added in the form of an oxide or a mixture of oxides and hydroxides which will form the alkaline earth hydroxide upon contact with a polar solvent selected from the protic solvents mentioned above.

[0036] The particulate material provided in step (a) typically comprises a lithium-containing transition metal oxide material, for example material obtained from lithium-ion battery waste after a preliminary step (i) of heating under inert or reducing conditions to a temperature in the range of 80-900° C., for example 200-850° C., especially 200-800° C. As explained in more detail below, the preliminary step (i) is typically carried out immediately after discharging, dismantling and / or crushing the lithium-ion batteries. In some applications, crushing and / or dismantling is carried out after the preliminary step (i). The lithium-ion batteries used, and thus the particulate material provided in step (a), typically contain carbon, for example in the form of graphite.

[0037] For example, for the treatment of a material in this step (i), where an elevated temperature is mentioned, the exposure time, if indicated, defines the total residence time in the reactor or furnace being heated to said elevated temperature, and the temperature of the material should reach a temperature in the given range for at least a fraction of said residence time.

[0038] Unless otherwise specified, "containing" with respect to any substance generally means that such substance is present in an amount still detectable, typically by x-ray powder diffraction, e.g., 1% by weight or more, or that such constituents are present in an amount detectable, typically by ICP after suitable digestion, e.g., 10 ppm by weight or more. The particulate material provided in this step (a) typically contains, by element, about 1-10% lithium, about 3-30% of a combination of transition metal elements, cobalt and / or nickel, and about 4-40% of all transition metal elements, including any cobalt, nickel, manganese, copper and iron (all by weight percentages of the dry particulate material provided in step (a)).

[0039] In the following, the particulate material provided in step (a) and the material subjected to step (i) are alternatively collectively referred to as a lithium-containing transition metal oxide material.

[0040] Carbon-containing materials may be used as reducing agents in the pretreatment of the reduction described above. Other reducing agents useful for providing a reducing gas stream for this preliminary step (i) are as described in JP 2012-229481, with hydrogen and / or carbon monoxide being preferred. The present invention thus includes a method comprising the above steps (i) and (a), (b) and (c) and (d), wherein the heating step (i) is carried out under reducing conditions comprising the presence of carbon and / or a reducing gas selected from hydrogen, methane and carbon monoxide.

[0041] Step (i) Method 1 When hydrogen is used as the reducing gas, the preliminary step (i) is preferably carried out as follows: (i) heating the lithium-containing transition metal oxide material in the presence of H2 to a temperature in the range of 200 to 900°C, or as indicated above.

[0042] Typically, the lithium-containing transition metal oxide material heated in step (i) originates from a lithium ion battery and may typically contain fluorine in the range of 1% by weight to 8% by weight, and / or phosphorus in the range of 0.2% by weight to 2% by weight, based on the weight of the lithium-containing transition metal oxide material.

[0043] Step (i), which is carried out with hydrogen, comprises heating the lithium-containing transition metal oxide material to a temperature in the range of 200 to 900°C, preferably 300 to 600°C, more preferably 350 to 500°C. In general, it is preferred not to expose the lithium-containing transition metal oxide material to temperatures above 500°C, since strong heating, especially under oxidizing conditions and to a lesser extent also under reducing atmospheres, tends to increase the formation of insoluble species (e.g. LiMnO2). As a result, it is preferred to keep the temperature in step (i) below 500°C, and in one embodiment of the method, step (i) is carried out with hydrogen at a temperature in the range of 350 to 450°C, for example 380 to 450°C, especially 380 to 440°C. The atmosphere used to carry out the reduction contains, according to this embodiment, 0.1% to 100% by volume of hydrogen, the remainder being a non-oxidizing gas, preferably nitrogen, argon, water vapor, carbon monoxide, carbon dioxide, or a mixture of at least two of these gases. Preferred non-oxidizing gases are nitrogen and water vapor, and mixtures of nitrogen and water vapor. In a preferred embodiment, step (i) of the process is carried out mainly under hydrogen, for example in an atmosphere containing 35-100% by volume, preferably 50-100% by volume (normal conditions) of hydrogen, the remainder being non-oxidizing gas, if any. In this embodiment of the invention, step (i) has a duration (residence time) in the range of 10 minutes to 30 hours, preferably 20 minutes to 8 hours, more preferably 30 minutes to 4 hours. The duration of step (i), preferably in the presence of hydrogen, lasting 20 to 90 minutes, is of special technical interest.

[0044] The concentration of hydrogen in the reducing atmosphere and the reaction time are interdependent: usually, a lower concentration of hydrogen requires a longer reduction time and vice versa.

[0045] Thus, in a preferred method of the invention, step (i) is carried out by heating the lithium-containing transition metal oxide material to a temperature in the range of 350-450° C. in the presence of more than 35% by volume, particularly 50-100% by volume, of H2 for a period of 20-90 minutes. Within the present invention, a particularly preferred method is to carry out step (i) at a temperature between 400° C. and 450° C., for example between 400° C. and 420° C., for up to 2.5 hours using 35% by volume or more of hydrogen, in order to recover Li in a particularly efficient manner in step (b), although applying a temperature that is too high may result in a low yield, and a long duration, although without any negative effects, tends to reduce the space-time yield, and a H2 concentration of 35% by volume or more is preferred as it leads to a short reaction time of 2.5 hours or less, and an optimal space-time yield can be achieved using more than 80% by volume of hydrogen.

[0046] After the heat treatment, the material is transferred from the oven to a cooling unit. Here, the material is cooled, preferably to a temperature below 100°C. Cooling can be performed at ambient conditions, for example by storing the hot material in a chamber or container or in a rotating tube, which may be the last unheated or cooled part of a rotary kiln, where the heat treatment is performed and the heat can be transferred to the environment. Preferably, the hot material can be cooled and conveyed by a cooling conveying screw. A more rapid cooling can be obtained by introducing a gas, which can be fed to the heat exchanger after passing through the hot material bed. Such gas cooling can be designed as a fixed bed, a moving bed or a fluidized bed. The gas used is preferably an inert gas, such as nitrogen, argon or carbon dioxide. It is also possible to use a reducing gas, which is preferably used for reduction at the beginning of the cooling period, when the material is still at a temperature close to the oven temperature. Afterwards, the gas composition can be changed to an inert gas at a lower temperature, or even an oxygen-containing gas, such as air, or a mixture of air and an inert gas can be used.

[0047] Alternatively, the hot material can be quenched with a liquid for cooling under dry conditions in a gas atmosphere. Quenching can be carried out by spraying the hot material with a cooling liquid, either in an amount where the liquid evaporates and the material remains essentially dry (evaporative cooling), or in a larger amount where a slurry of the material is formed. Cooling with a liquid is particularly preferred when the resulting cooled material or slurry can be used directly for step (b) of the invention. Thus, the preferred quench liquid is a sufficiently temperature stable polar solvent, with water being most preferred. The liquid can be pumped through a heat exchanger and recycled back to the cooling vessel.

[0048] Step (i) Method 2 When using a carbon-based material, such as carbon, as the reducing agent, the preliminary step (i) is preferably carried out as follows: (i) heating the lithium-containing transition metal oxide material in the presence of the carbon-based material, such as carbon, for example in the presence of graphite, to a temperature in the range of 200 to 900° C. In a preferred embodiment of the present invention, graphite contained in the black mass is used as the reducing agent.

[0049] As explained in more detail below, typically the lithium-containing transition metal oxide material heated in step (i) originates from a lithium ion battery and may contain typical impurities such as fluorine.

[0050] Step (i), which is carried out using a carbon-based material, such as carbon, as a reducing agent, comprises heating the lithium-containing transition metal oxide material to a temperature in the range of 200 to 900°C, preferably 300 to 850°C, more preferably 500 to 850°C.

[0051] The atmosphere used to carry out the reduction, according to this embodiment, either does not contain oxygen or contains up to 20% by volume of oxygen, the remainder being a non-oxidizing gas, preferably nitrogen, argon, water vapor, carbon monoxide, carbon dioxide or a mixture of at least two of these gases. Preferred non-oxidizing gases are nitrogen and carbon monoxide, and mixtures of nitrogen and carbon monoxide. In a preferred embodiment, step (i) of the process is carried out under air or diluted air, for example in an atmosphere containing 1 to 20% by volume, preferably 1 to 10% by volume of oxygen (normal conditions), the remainder being a non-oxidizing gas, if present. In this embodiment of the invention, step (i) has a duration in the range of 10 minutes to 30 hours, preferably 20 minutes to 8 hours, more preferably 30 minutes to 4 hours. The duration of step (i), preferably in the presence of carbon, lasting 20 to 120 minutes, especially 30 to 120 minutes, is of special technical interest.

[0052] After the heat treatment, the material is transferred from the oven to a cooling unit. Here, the material is cooled, preferably to a temperature below 100°C. Cooling can be performed at ambient conditions, for example by storing the hot material in a chamber or container or in a rotating tube, which may be the last unheated or cooled part of a rotary kiln, where the heat treatment is performed and the heat can be transferred to the environment. Preferably, the hot material can be cooled and conveyed by a cooling conveying screw. A more rapid cooling can be obtained by introducing a gas, which can be fed to the heat exchanger after passing through the hot material bed. Such gas cooling can be designed as a fixed bed, a moving bed or a fluidized bed. The gas used is preferably an inert gas, such as nitrogen, argon or carbon dioxide. It is also possible to use a reducing gas, which is preferably used for reduction at the beginning of the cooling period, when the material is still at a temperature close to the oven temperature. Afterwards, the gas composition can be changed to an inert gas at a lower temperature, or even an oxygen-containing gas, such as air, or a mixture of air and an inert gas can be used.

[0053] Alternatively, the hot material can be quenched with a liquid for cooling under dry conditions in a gas atmosphere. Quenching can be carried out by spraying the hot material with a cooling liquid, either in an amount where the liquid evaporates and the material remains essentially dry (evaporative cooling), or in a larger amount where a slurry of the material is formed. Cooling with a liquid is particularly preferred when the resulting cooled material or slurry can be used directly for step (b) of the invention. Thus, the preferred quench liquid is a sufficiently temperature stable polar solvent, with water being most preferred. The liquid can be pumped through a heat exchanger and recycled back to the cooling vessel.

[0054] In one embodiment of the present invention, the reduction conditions relate to hydrogen and / or carbon / oxygen concentrations, and the temperature and duration of step (i) are selected such that at least a portion of the lithium-containing transition metal oxide material contains paramagnetic, antiferromagnetic, ferromagnetic and / or ferrimagnetic components. The formation of ferromagnetic or ferrimagnetic components resulting from at least partial reduction of the lithium-containing transition metal material is preferred. The degree of reduction can vary in the range of 1-100% with respect to the nickel contained in the lithium-containing transition metal material, but is preferably in the range of 80-100%.

[0055] Thus, the particulate material provided in step (a) contains a transition metal compound and / or a transition metal selected from the group consisting of Mn, Ni and / or Co, and further wherein at least a portion of the Ni and / or Co, if present, is in an oxidation state lower than +2, and wherein at least a portion of the Mn, if present, is manganese (II) oxide, in which the nickel and / or cobalt is typically, at least in part, present in the metallic state.

[0056] The presence of phases in oxidation states lower than +2, such as Ni and / or Co, Mn in the form of manganese(II) oxide, and nickel and / or cobalt as metal, can be detected by XRD, as described further below.

[0057] The lithium salts present in the particulate material provided in step (a) are detected by standard methods as described below. The lithium salts contained in the particulate material provided in step (a) typically include one or more of LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, lithium phosphate salts, mixed oxides of Li and one or more of Ni, Co, Mn, Fe, Al, Cu, and / or fluorides of Ni, Co, Mn, Fe, Al, Cu.

[0058] LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate and lithium phosphate typically account for 95% or more by weight of the total lithium salts present. When the particulate material prepared in step (a) is derived from a lithium-ion battery or part thereof, LiF, Li2CO3, LiOH and lithium aluminate are very often included. If present, a larger proportion of fluoride, for example 50% or more by weight of said fluoride, is typically present as lithium fluoride. The fluoride salts present typically come partly from the electrolyte salts and polymeric binders of former batteries, and hydrogen fluoride is liberated during the preliminary steps of discharging or dismantling or drying the battery materials, and other types of fluoride salts, such as cobalt fluoride, may also be present from the rapid reaction of hydrogen fluoride with former cell or electrode materials.

[0059] The particulate material provided in step (a) is generally a material derived from a battery material containing lithium and one or more transition metals including nickel and / or cobalt, such as a lithium-ion battery or a part of a lithium-ion battery, in particular a cell material thereof. For step (a), the material is provided in the form of a dry powder, a wet powder or a suspension of particles in a liquid. The material typically has an average particle diameter (D50 according to ISO 13320 EN:2009-10) in the range of 1 μm to about 2 mm, in particular 1 μm to 1 mm. In a typical method, an upper limit on the size of the particles in the powder material is given by a sieving step carried out before step (a) or even before step (i), for example using a sieve that allows particles of up to 2 mm, in particular up to 1 mm, to pass through the mesh.

[0060] Typically, the lithium-containing transition metal oxide material is obtained after mechanically removing the casing, wiring or circuitry, and therefore typically consists mainly of cell material. For safety reasons, such lithium-ion batteries are fully discharged or electrically discharged at least 80% (preferably more than 90%, most preferably more than 95%), for example by immersion in a dry conductive bath, for example metal strips, so that residual electrical energy can be recovered, which otherwise may cause short circuits that constitute a fire and explosion hazard. Such lithium-ion batteries can be disassembled, punched, crushed, for example in a hammer mill, or crushed, for example in an industrial shredder. Although not preferred, the batteries can also be discharged by immersing them in a conductive liquid, for example an aqueous solution of a metal salt, such as sodium sulfate. Crushing can also be carried out in a liquid, preferably in water. This has the advantage of preventing dust formation and the generation of an ignitable atmosphere.

[0061] Before subjecting the material to the preliminary step (i), it may be advantageous to at least partially remove the electrolyte, in particular the electrolyte comprising an organic solvent or a mixture of organic solvents, for example by drying at subatmospheric pressure, for example at a temperature in the range of 50-250° C. As mentioned above, the lithium-containing transition metal oxide material is preferably not exposed to high temperatures (in particular above 400° C.) under oxidizing conditions before being subjected to this step (a).

[0062] Nevertheless, in one embodiment of the present invention, prior to the reduction step (i), a heat treatment may be carried out under oxidizing conditions. This treatment may be carried out in a temperature range of 250-900°C, preferably between 350°C and 800°C, for example 300-400°C. To achieve oxidizing conditions, air or an oxygen-containing gas may be introduced into the reactor. The oxidation treatment may be carried out in the presence of alkaline earth hydroxides or oxides. The reaction may also be carried out in the presence of water as steam, thus applying hydrothermal conditions.

[0063] In one embodiment of the present invention, the lithium-containing transition metal oxide material is derived from battery scrap. In a preferred embodiment of the present invention, the lithium-containing transition metal oxide material is derived from mechanically treated battery scrap, for example, battery scrap treated in a hammer mill or industrial shredder. This mechanical treatment can be carried out under dry or wet conditions, preferably in the presence of water.

[0064] In one embodiment of the invention, step (a) is preceded by step (a1), which step (a1) comprises, for example, removing carbon or organic polymers by a solid-solid separation method. Examples of such solid-solid separation methods are electric sorting, sieving, magnetic separation, flotation or other classification methods. Solid-solid separation can be carried out dry or in the presence of a suitable carrier medium, preferably water.

[0065] In one embodiment of the present invention, the mechanically treated battery scrap is ground prior to step (a). Such grinding is preferably carried out in a ball mill or an agitated ball mill. Milling can be carried out under wet or dry conditions, with dry conditions being preferred.

[0066] In one embodiment of the present invention, prior to step (a), the mechanically treated battery scrap is contacted with water and / or an organic solvent, followed by a solid-liquid separation step.

[0067] In one embodiment, the mechanically treated battery scrap is contacted with a basic or acidic solution to facilitate the peeling of the active material from the electrode foil, as described in WO 2018 / 192122.

[0068] In one embodiment of the present invention, prior to the thermal treatment of step (i), the mechanically treated battery scrap is subjected to a solvent treatment in order to dissolve and separate the polymeric binder used to bind the lithium transition metal oxide to the current collector film. Suitable solvents are N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and N-ethylpyrrolidone, dimethylsulfoxide, hexamethyl phoshoramide, tetramethylurea, trimethylphosphate and triethylphosphate, in pure form or as a mixture.

[0069] The solvent treatment can be carried out with one or more solvents in successive steps or in one step utilizing a solvent capable of dissolving the electrolyte components and the binder polymer. The solvent is applied in a temperature range of 10° C. to 200° C. In particular, dissolution of the polymer may require elevated temperatures ranging from 50 to 200° C., preferably between 100° C. and 150° C. The upper temperature limit is usually limited by the boiling point of the solvent, unless pressures higher than 1 bar are applied.

[0070] In one embodiment, the cleaning of mechanically processed battery scrap is carried out with an aprotic solvent under the absence of moisture, for example, under a dry gas such as dry air or dry nitrogen.

[0071] In a typical embodiment of the present invention, the lithium-containing transition metal oxide material includes battery scrap material, parts of a lithium-ion battery or materials from parts, off-specification materials including pure electrode materials, or mixtures of such materials. However, the lithium-containing transition metal oxide material preferably contains, when applicable, within the range of 0.1 to 80% by weight, a nickel compound, such as a nickel / cobalt component, or a compound other than a nickel / cobalt / manganese or nickel / cobalt / aluminum compound, and in extreme cases, valuable materials are in minority components. Examples of such components are carbon in an electrically conductive form, also referred to hereinafter as conductive carbon, such as graphite, soot, and graphene. Further examples of impurities are copper and its compounds, aluminum and aluminum compounds, such as alumina, iron and iron compounds, zinc and zinc compounds, silicon and silicon compounds, such as silica and silicon oxide SiO y [zero < y ≦ 2], tin, silicon-tin alloys, and organic polymers, such as polyethylene, polypropylene, and fluorinated polymers, such as polyvinylidene fluoride, tetrafluoroethylene polymers, etc. Further impurities are fluorine compounds, such as inorganic fluorides, and phosphorus compounds that may be derived from the liquid electrolyte, such as widely used LiPF6 and impurities in the products derived from the hydrolysis of LiPF6. The battery scrap serving as the starting material for the method of the present invention may be derived from multiple sources, and thus, in the majority of embodiments, the lithium-containing transition metal oxide material contains, when applicable, a nickel / cobalt compound, or a compound other than a nickel / cobalt / manganese or nickel / cobalt / aluminum component, and one of such components is carbon in an electrically conductive form within the range of 2 to 65% by weight with respect to the entire lithium-containing transition metal oxide material.

[0072] In an exemplary embodiment of the present invention, the lithium-containing transition metal oxide material contains one or more of the following additional components or impurities: i) copper, either as metal or in the form of one or more of its compounds, in the range of 20 ppm to 10% by weight, in particular 20 ppm to 3% by weight; ii) aluminum in the form of one or more of the metal or its compounds, in the range of 100 ppm to 15% by weight; iii) iron in the form of one or more of the metal or alloys or compounds thereof, in the range of 100 ppm to 5% by weight; iv) zinc in the form of one or more of the metal or alloys or compounds thereof, in the range of 20 ppm by weight to 2% by weight; v) zirconium in the form of one or more of the metal or alloys or compounds thereof, in the range of 20 ppm by weight to 2% by weight; vi) fluorine, calculated for example as the sum of the organic fluorine bound to the polymer and the inorganic fluoride in one or more of the inorganic fluorides, in the range of 1% to 8% by weight, in particular 2% to 8% by weight, vii) in the range of 0.2% to 2% by weight of phosphorus, which may appear in one or more inorganic compounds; viii) Manganese in the form of one or more of the metal or its compounds, in the range of 100 ppm by weight to 15% by weight.

[0073] Examples of such embodiments include one or two of the above additional components, or additional components (i), (ii) and (iii); (i), (ii) and (iv); (i), (ii) and (v); (i), (ii) and (vi); (i), (ii) and (viii); (i), (iii) and (iv); (i), (iii) and (v); (i), (iii) and (vi); (i), (iii) and (vii); (i), (iii) and (viii); (i), (iv) and (v); (i), (iv) and (vi); (i), (iv) and (vii); (i), (iv) and (viii); (i), (v) and (vi); (i), (v) and (vii); (i), (iv) and (viii); (i), (v) and (vi); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (v) and (vii); (i), (vii) and (viii); (i), (ii), (iii) and (iv); (i), (ii), (iii) and (v); (i), (ii), (iii) and (vi); (i), (ii), (iii) and (vii); (i), (ii), (iii) and (viii); (i), (ii), (iv) and (v); (i), (ii), (iv) and (vi); (i), (ii), (iv) and (vii); (i), (ii), (iv) and (viii); (i), (ii), (v) and (vi); (i), (ii), (v) and (vii); (i), (ii), (v) and (viii); (i), (ii), (v) and (vii); (i), (ii), (v) and (viii); (i), (ii), (vi) and (vii); (i), (ii), (vi) and (viii); (i), (ii), (vii) and (viii); (i), (iii), (iv) and (v); (i), (iii), (iv) and (vi); (i), (iii), (iv) and (vii); (i), (iii), (iv) and (viii); (i), (iii), (v) and (vi); (i), (iii), (v) and (vii); (i), (iii), (v) and (viii); (i), (iii), (vi) and (vii); (i), (iii), (vi) and (vii); (i), (iii), (vi) and (viii); (i), (iii), (vii) and (viii); (i), (iii), (vii) and (viii); (i), (iv), (v) and (vii); (i), (iv), (v) and (vii); (i), (iv), (v) and (viii);(i), (iv), (vi) and (vii); (i), (iv), (vi) and (viii); (i), (iv), (vii) and (viii); (i), (v), (vi) and (vii); (i), (v), (vi) and (viii); (i), (v), (vii) and (viii); (i), (vi), (vii) and (viii); (i), (vi), (vii) and (viii); (ii), (iii), (iv) and (v); (ii), (iii), (iv) and (vii); (ii), (iii), (iv) and (vii); (ii), (iii), (iv) and (viii); (ii), (iii), (v) and (vi); (ii), (iii), (v) and (vii); (ii), (iii), (iv) and (viii); (ii), (iii), (v) and (vi); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (vii); (ii), (iii), (v) and (viii); (ii), (iii), (vi) and (vii); (ii), (iii), (vi) and (viii); (ii), (iii), (vii) and (viii); (ii), (iv), (v) and (vi); (ii), (iv), (v) and (vii); (ii), (iv), (v) and (viii); (ii), (iv), (vi) and (vii); (ii), (iv), (v) and (viii); (ii), (iv), (vii) and (vii); (ii), (iv), (vi) and (viii); (ii), (iv), (vii) and (viii); (ii), (v), (vii) and (vii); (ii), (v), (vii) and (viii); (ii), (vi), (vii) and (viii); (ii), (vi), (vii) and (viii); (iii), (iv), (v) and (vi); (iii), (iv), (v) and (vii); (iii), (iv), (v) and (viii); (iii), (iv), (vi) and (vii); (iii), (iv), (vi) and (viii); (iii), (iv), (vii) and (viii); (iii), (v), (vi) and (vii); (iii), (v), (vi) and (viii); (iii), (v), (vii) and (viii); (iii), (v), (vii) and (viii); (iii), (vi), (vii) and (viii); (iii), (vi), (vii) and (viii); (iv), (v), (vi) and (vii); (iv), (v), (vi) and (viii); (iv), (v), (vii) and (viii); (iv), (vi), (vii) and (viii); (iv), (vi), (vii) and (viii); (v), (vii) and (viii);(i), (ii), (iii), (iv) and (v); (i), (ii), (iii), (iv) and (vi); (i), (ii), (iii), (iv) and (vii); (i), (ii), (iii), (iv) and (viii); (i), (ii), (iii), (iii), (v) and (vii); (i), (ii), (iii), (v) and (viii); (i), (ii), (iii), (iii), (vi) and (vii); (i), (ii), (iii), (iii), (vi) and (viii); (i), (ii), (iii), (iii), (vi) and (vii); (i), (ii), (iii), (iii), (vi) and (viii); (i), (ii), (iii), (iii), (vii) and (viii); (i), (ii), (iii), (iv), (v) and (vii); (i), (ii), (iv), (v) and (viii); (i), (ii), (iv), (vi) and (vii); (i), (ii), (iv), (vi) and (viii); (i), (ii), (iv), (vii) and (viii); (i), (ii), (v), (vi) and (vii); (i), (ii), (v), (vi) and (vii); (i), (ii), (v), (vii) and (viii); (i), (ii), (v), (vii) and (viii); (i), (ii), (vi), (vii) and (viii); (i), (iii), (iv), (v) and (vi); (i), (iii), (iv), (v) and (vii); (i), (iii), (iv), (v) and (vii); (i), (iii), (iv), (v) and (vii); (i), (iii), (iv), (v) and (viii); (i), (iii), (iv), (vi) and (vii); (i), (iii), (iv), (vi) and (viii); (i), (iii), (iv), (vii) and (viii); (i), (iii), (v), (vi) and (vii); (i), (iii), (v), (vi) and (viii); (i), (iii), (vi), (vii) and (viii); (i), (iv), (v), (vii) and (vii); (i), (iv), (v), (vi), (vii) and (vii); (i), (iv), (v), (vi), (vii) and (viii); (i), (iv), (v), (vii) and (viii); (i), (iv), (vi), (vii) and (viii); (i), (v), (vii) and (vii); (i), (v), (vii), (vii) and (viii); (ii), (iii), (iv), (v) and (vii);(ii), (iii), (iv), (v) and; (viii); (ii), (iii), (iv), (vi) and (vii); (ii), (iii), (iv), (vi) and (viii); (ii), (iii), (iv), (vii) and (viii); (ii), (iii), (v), (vi) and (vii); (ii), (iii), (v), (vi) and (viii); (ii), (iii), (v), (vii) and (viii); (ii), (iii), (vi), (vii) and (viii); (ii), (iv), (v), (vi) and (vii); (ii), (iv), (v), (vi) and (viii); (ii), (iv), (v), (vii) and (viii); (ii), (iv), (vi), (vii) and (viii); (ii), (v), (vi), (vii) and (viii); (iii), (iv), (v), (vi) and (vii); (iii), (iv), (v), (vi) and (viii); (iii), (iv), (v), (vii) and (viii); (iii), (iv), (vi), (vii) and (viii); (iii), (v), (vi), (vii) and (viii); (iv), (v), (vi), (vii) and (viii); (i), (ii), (iii), (iv), (v) and (vi); (i), (ii), (iii), (iv), (v) and (vii); (i), (ii), (iii), (iv), (v) and (viii); (i), (ii), (iii), (iv), (vi) and (vii); (i), (ii), (iii), (iv), (vi) and (viii); (i), (ii), (iii), (iv), (vii) and (viii); (i), (ii), (iii), (v), (vi) and (vii); (i), (ii), (iii), (v), (vi) and (viii); (i), (ii), (iii), (v), (vii) and (viii); (i), (ii), (iii), (vi), (vii) and (viii); (i), (ii), (iv), (v), (vi) and (vii); (i), (ii), (iv), (v), (vi) and (viii); (i), (ii), (iv), (v), (vii) and (viii); (i), (ii), (iv), (vi), (vii) and (viii);(i), (ii), (v), (vi), (vii) and (viii); (i), (iii), (iv), (v), (vi) and (vii); (i), (iii), (iv), (v), (vi) and (viii); (i), (iii), (iv), (v), (vii) and (viii); (i), (iii), (iv), (vi), (vii) and (viii); (i), (iii), (v), (vi), (vii) and (viii); (i), (iv), (v), (vi), (vii) and (viii); (ii), (iii), (iv), (v), (vi) and (vii); (ii), (iii), (iv), (v), (vi) and (viii); (ii), (iii), (iv), (v), (vii) and (viii); (ii), (iii), (iv), (vi), (vii) and (viii); (ii), (iii), (v), (vi), (vii) and (viii); (ii), (iv), (v), (vi), (vii) and (viii); (iii), (iv), (v), (vi), (vii) and (viii); (i), (ii), (iii), (iv), (v), (vi) and (vii); (i), (ii), (iii), (iv), (v), (vi) and (viii); (i), (ii), (iii), (iv), (v), (vii) and (viii); (i), (ii), (iii), (v), (vi), (vii) and (viii); (i), (ii), (iv), (v), (vi), (vii) and (viii); (i), (iii), (iv), (v), (vi), (vii) and (viii); (ii), (iii), (iv), (v), (vi), (vii) and (viii). Another example is a lithium-containing transition metal oxide material containing each of the above additional components;

[0074] Each of the percentages given above is by weight of the dry material (ie, the lithium-containing transition metal oxide material provided in this step (a)).

[0075] In an embodiment of particular technical interest, the particulate material provided in step (a) contains only small amounts of calcium or no calcium at all. Such transition metal compounds and / or transition metal-containing particulate materials may further contain lithium salts and fluoride salts, and may optionally contain calcium, so long as the elemental ratio of calcium to fluorine is less than or equal to 1.7 or zero.

[0076] The lithium-containing transition metal oxide material typically contains nickel or cobalt, or both nickel and cobalt. Examples of lithium-containing transition metal oxide materials may be based on lithiated nickel cobalt manganese oxide ("NCM") or lithiated nickel cobalt aluminum oxide ("NCA"), or mixtures thereof.

[0077] Examples of layered nickel-cobalt-manganese oxides are those of the general formula Li 1+x (Ni a Co b Mn c M 1 d ) 1-x O2 compound, M 1 is selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Mo, V and Fe, and further variables are defined as follows: Zero≦x≦0.2 0.1≦a≦0.95, Zero ≦ b ≦ 0.9, preferably 0.05 <b≦0.5、 zero ≦ c ≦ 0.6, Zero≦d≦0.1 and a+b+c+d=1.

[0078] In a preferred embodiment, in the compound according to general formula (I), Li (1+x) [Ni a Co b Mn c M 1 d ] (1-x) O2(I) M 1is selected from Ca, Mg, Zr, Al, Ti and Ba; Further variables are defined as above.

[0079] An example of a lithium nickel-cobalt aluminum oxide is represented by the general formula Li[Ni h Co i Al j ]O 2+r Typical values ​​for r, h, i and j are: h is in the range of 0.8 to 0.95, i is in the range of 0.02 to 0.3, j is in the range of 0.01 to 0.10, r is in the range of zero to 0.4.

[0080] Li (1+x) [Ni 0.33 Co 0.33 Mn 0.33 ] (1-x) O2, Li (1+x) [Ni 0.5 Co 0.2 Mn 0.3 ] (1-x) O2, Li (1+x) [Ni 0.6 Co 0.2 Mn 0.2 ] (1-x) O2, Li (1+x) [Ni 0.7 Co 0.2 Mn 0.1 ] (1-x) O2, Li (1+x) [Ni 0.8 Co 0.1 Mn 0.1 ] (1-x) O2 (wherein x is as defined above), and Li[Ni 0.85 Co 0.13 Al 0.02 ]O2 is particularly preferred.

[0081] The lithium-containing transition metal oxide material may have a regular shape, but usually has an irregular shape. However, it is preferable to remove light parts, such as organic plastic housing parts and aluminum or copper foil, as much as possible, for example in a forced gas flow.

[0082] In one embodiment, the composition of the atmosphere is changed during step (i), which may be done before switching the atmosphere to a reducing atmosphere, such as a hydrogen-containing atmosphere, for example if volatile organic compounds are present in the feed which are stripped in the inert atmosphere.

[0083] In one embodiment, an oxidizing atmosphere in the temperature range of 20-300° C. is used in step (i) prior to reduction with a hydrogen-containing atmosphere. This embodiment allows some impurity components, i.e. organic components, to be combusted or the material to be dried (among other things, as further described above, temperatures of up to 250° C. are utilized. The preferred oxidizing gas is oxygen or an oxygen-containing gas, such as air. Materials originating from spent lithium-ion battery cells, containing lithium, transition metal oxides, and typically fluorine and / or phosphorus compounds, are preferably not subjected to oxidation above 300° C. prior to carrying out the steps of the method.

[0084] In one embodiment of the invention, step (a) is preceded by step (a1), which comprises, for example, removing carbon or organic polymers by a dry solid-solid separation method. Examples of such dry solid-solid separation methods are electric sorting, sieving, magnetic separation or other classification methods, where step (a1) is introduced as an additional step.

[0085] In one embodiment of the present invention, the material provided in step (a) is ground prior to step (b) in order to deagglomerate the different solid particles from one another, if they are somewhat agglomerated, for example by residual binder polymer. The grinding can be carried out under dry or wet conditions. Preferably, the grinding is carried out in an aqueous medium which is also utilized in the subsequent step (b).

[0086] At the end of step (b), the pressure may be released if applicable. A solution of lithium salt is obtained from step (c) as a liquid, typically an aqueous solution containing LiOH.

[0087] Prior to this step (c), the solid residue is contained in a polar solvent, which may be an aqueous solution, to form a suspension. If the extraction of the Li-compound is carried out in two or more steps as described above, the solid residue will be contained in the slurry of the second or last step, respectively.

[0088] The solid residue obtained in step (c) is recovered by a solid-liquid separation step (c), which may be a type of filtration or centrifugation, or settling and decantation, optionally followed by a washing step, in which the respective polar solvent used as washing medium in step (b) is applied. The filtrate and the washing liquid are usually combined before further work up of the respective lithium salt. To recover such solid material, which contains fine particles, for example with an average diameter of 50 μm or less, a flocculating agent, for example polyacrylate, may be added.

[0089] The solid residue obtained by step (c) is characterized by a typical elemental composition resulting from the application of the preferred process conditions during step (b). In particular, the solid residue is characterized by a composition typical of battery scrap material (Li, graphite and at least one of Ni and Co, Mn may also be present), but with a significantly higher (Ni + Co + Mn) to Li weight ratio. Since the battery scrap material, especially the cathode active material, is characterized by a (Ni + Co + Mn):Li weight ratio between 5 and 12, the solid residue after step (c) is characterized by a lower Li content, and therefore a (Ni + Co + Mn):Li weight ratio between 13 and 100000. Furthermore, the preferred process in step (b) is accompanied by a significant increase in the calcium content, which, as mentioned above, is very low (0-0.5 wt%) in the initial particulate material prepared in step (a). The solid residue obtained by this preferred variant of step (c) is characterized by an elemental Ca weight content of between 2% and 50% by weight (based on the dry solids).

[0090] This solid residue obtainable by step (c) is a source of valuable materials useful for the production of new batteries, and steps for the isolation of such materials are described below.

[0091] The solid residue obtained by step (c) may subsequently be subjected to a step (d1) of adjusting, inter alia, the amount of carbon it contains. This can be achieved by solid-solid separation or by thermal treatment in which the carbon is burned in an oxygen-containing gas, for example air. Such a combustion process may be integrated into the smelting process of step (d) by utilizing an oven with different heating zones and temperature regimes, an example being a blast furnace, where the material is placed in a pre-heating zone of the oven at temperatures between 500 and 900° C., under conditions in which at least a portion of the carbonaceous material is burned.

[0092] When step (d1) of the present invention comprises a solid-solid separation step, it may be a wet solid-solid separation step. This solid-solid separation step serves to separate insoluble components such as carbon and polymers, or insoluble inorganic components such as metal oxide particles, from the metal or metal oxide components of the lithium-containing transition metal oxide material. After said solid-solid separation of step (d1), a solid concentrate fraction is obtained, which contains the majority of Ni and / or Co in concentrated form. Such a solid-solid separation step may be carried out mechanically, by column or pneumatic means, or by combined flotation. In many embodiments, collector compounds are added to the slurry to make the target components hydrophobic. Typical collector compounds for carbon and polymer particles are hydrocarbons or fatty alcohols, which are introduced in amounts of 1 g to 50 kg per ton of solid residue obtained from step (c). Flotation can also be carried out in the opposite sense, i.e. by converting the originally hydrophilic components into strongly hydrophobic ones by special collectors, e.g. fatty alcohol sulfates or esterquats. Direct flotation using hydrocarbon collectors, e.g. mineral oil, kerosene or diesel oil, is preferred. In order to improve the selectivity of the flotation towards carbon and polymer particles, inhibitors can also be added, which reduce the amount of metal and metal oxide components entrained in the foam phase. Agents that can be used can be acids or bases to control the pH value within the range of 3 to 9. They can also be ionic components, e.g. sodium silicate, which adsorb to the metal or metal oxide surfaces, or bipolar components, e.g. amino acids. To increase the efficiency of the flotation, it can be advantageous to add carrier particles, e.g. polymer particles, carbonaceous particles, e.g. graphite or coal, which form agglomerates with the hydrophobic target particles. By using magnetic carrier particles, magnetic agglomerates can be formed which can be separated magnetically.If the target components are paramagnetic, antiferromagnetic, ferrimagnetic, or ferromagnetic, they can also be separated by magnetic separation using high-intensity magnetic separators ("WHIMS"), medium-intensity magnetic separators ("MIMS"), or low-intensity magnetic separators ("LIMS"). Other solid-solid separation techniques use density differences of solid components, for example the density difference between graphite and metals or metal oxides. These techniques include sink-float methods, which utilize a fluid of intermediate density to that of the solid components to be separated. Another technique in this class is heavy liquid separation. Further separation techniques based on density differences are spirals and hydrocyclones.

[0093] Combinations of at least two of the aforementioned solid-solid separation techniques can also be utilized. These combinations may include roughing, cleaning and cleaning steps typical of mineral processing flowsheets. Also, a combination of solid-solid separation and a carbon combustion step can be envisaged.

[0094] In a preferred embodiment, the solid-solid separation in step (d1) is a magnetic separation.

[0095] In one embodiment of the present invention, the solid material resulting from step (c) is ground prior to step (d1) in order to free different solid particles from one another if they are somewhat agglomerated, for example by residual binder polymer. Such grinding is preferably carried out in a ball mill or stirred ball mill.

[0096] In one embodiment of the present invention, step (d1) is a wet solid-solid separation utilizing an aqueous medium, preferably water, as the fluid. The weight ratio of the fluid medium to the solid material in such step (d1) is typically in the range of 1:1 to 99:1, preferably 2:1 to 9:1.

[0097] The wet solid-solid separation of step (d1) results in two slurries: one containing the target transition metal-containing solid material and the other containing other components such as carbonaceous materials and polymers and, if applicable, also some inorganic compounds. By suitable selection and, if necessary, combination of solid-solid separation steps, at least 60% of the Ni and / or Co is obtained and concentrated in one fraction. Preferably, at least 80-99% of the Ni and / or Co is separated. The carbon content in the metal-containing fraction is significantly reduced but is typically more than 5% by weight, for example 5-20% by weight.

[0098] The solid material recovered in step (c) or (d1) is a particulate material that may contain residual liquid, e.g. water. In one embodiment of the present invention, this material is dried to a residual liquid content of less than 5% by weight (% bw), preferably less than 1% by weight, before being introduced in step (d). In another embodiment, the solid residue obtained in step (c) will be agglomerated into spherical or cylindrical particles with a diameter in the range of 1-20 mm, preferably 2-8 mm. To produce such pellets that are mechanically stable enough to be introduced in the melting oven in step (d), the agglomeration of the particulate material is achieved by adding a binder. Such binders are preferably inorganic binders, such as, for example, bentonite or gamma-alumina, or a mixture of at least two of these materials. Organic polymeric binders can also be applied based on starch, cellulose, molasses, lignin, polyacrylates, waxes, or a mixture of at least two of these materials. Mixtures of inorganic and organic binders are also suitable. In addition to these binders, slag-forming additives such as quartz alumina and / or limestone may already be added to the agglomerates. The agglomerates may be formed by extrusion or pelletizing in a drum or disk pelletizer, the latter two being preferred, as known in the art. The amounts of slag-forming additives and their ratios are selected to allow suitable slug formation. The slug composition can be modeled by commercially available software, for example FactSage®. Usually, pelletizing is carried out in the presence of water, and after the pellets are formed, they are dried and fired to obtain a hardened sintered body of sufficient mechanical stability.

[0099] The solid residue from step (c) or step (d1), preferably after pelletizing, drying and calcining, is fed to a smelter furnace. Typically, the feed is premixed with slag-forming additives and fluxes (e.g. soda, potash, lime, borax). Suitable smelter furnaces are bath smelters, top blown converters, blast furnaces, electric arc furnaces, plasma furnaces and others. The temperature in the furnace at the tapping point is typically between 1200°C and 1600°C. The furnace can be operated in a continuous or batch mode.

[0100] The solid residue from step (c) or (d1) may be mixed with nickel or cobalt concentrate obtained from ore, preferably from laterite, especially saprolite ore, and co-fed to the smelting unit.

[0101] The harvested alloy is typically fed (continuous or batch) to an underwater atomizer, granulator, or mold. The slag is typically fed to a slag cooling pool or underwater granulator, or atomized by a strong stream of gas into small droplets that cool on their way to the ground.

[0102] The furnace may be operated such that the solid residue resulting from step (c) or (d1) contains carbonaceous material that is combusted to provide the energy and reducing conditions for smelting. If the solid residue does not provide enough carbonaceous material, additional carburant, for example heavy mineral oil, can be fed to the oven. Such furnace operation is well known in the field of pyrometallurgy. Alternatively, the concentration level of carbonaceous material may be limited, for example to provide selective reduction of the target transition metal without over-reducing the melt and introducing deleterious components into the alloy.

[0103] The alloy thus obtained from smelting (d) contains metallic nickel and / or cobalt, and typically may also contain copper, iron, and also some manganese. Base metals such as aluminum are almost completely separated into the slag. Fluorine compounds are also trapped in the slag or separated into the flue gases from which the fluorides can be recovered by suitable scrubbers and filters.

[0104] The resulting alloy material may be further subjected to a hydrometallurgical process (step (f) to separate nickel and cobalt from copper). The separated nickel and cobalt, and manganese, if present, may be converted into metal salts, which may be used in the production of battery materials or for other applications.

[0105] In one embodiment of the invention, the liquid phase of the slurry fed to step (d1) still contains dissolved lithium. In this case, one or the other or both slurries resulting from the solid-solid separation in step (d1) are advantageously subjected to solid-liquid separation to recover the lithium solution. The lithium solution may then be further processed in step (e).

[0106] In step (e), the lithium-containing solution resulting from any of the steps described above, such as step (c) and / or step (d1), may be treated to recover lithium in the form of a solid material, either as a hydroxide or a salt.

[0107] In one embodiment of the present invention, the Li salt, in particular LiOH, is recovered by evaporation (e1) of the water contained in the solution, which may be carried out in two or more successive steps (e2 and e3 for example) to produce the Li salt of the desired high purity.

[0108] First, the Li-containing solution from any of the above steps is concentrated to near the point where the solubility limit of LiOH is reached. This step is accompanied by solid formation (e.g., crystallization) of impurities with lower solubility than LiOH, possible impurities can be, but are not limited to, Ca(OH)2, CaF2, CaCO3, LiF. These are separated by solid-liquid separation, e.g., by filtration or centrifugation, or by a type of settling and decantation. Since the residual amount of solids to be separated is small, a depth filter is preferably applied. Also a combination of two solid-liquid separation steps is possible, e.g., a hydrocyclone followed by a depth filter. If LiF precipitates during this first concentration step (e2), it is preferable to re-feed the solid material to step (b).

[0109] The filtrate obtained from the solid-liquid separation after one of the concentration steps, i.e. the concentrated LiOH solution, is then used in the next evaporation step (e3). High quality LiOH can be obtained by evaporating the remaining water and forming a LiOH solid. In case of crystallization, the crystals are again separated from the remaining mother liquor by solid-liquid separation and optionally washed. In order to concentrate the impurities, multiple crystallization steps followed by washing and solid-liquid separation are possible. Any mother liquor obtained from the crystallization can be subjected to further evaporation and crystallization and / or recycling by introducing the mother liquor into step (b) or (e1), (e2) or (e3).

[0110] All of the above solidification steps are advantageously followed by drying of the solid. Drying either below 60° C. or at higher temperatures under humid conditions results in LiOH monohydrate, otherwise at least partially anhydrous LiOH is obtained.

[0111] In that case, according to the described step (e1), the filtrate obtained after step (c) is dried by total evaporation of a polar solvent, e.g. water, to obtain LiOH (anhydrous or monohydrate) of high purity (>98.5%), which contains an impurity spectrum characteristic of the above processes, e.g. less than 0.35% by weight of carbonaceous impurities.

[0112] For LiOH monohydrate, the characteristic impurities are calcium, fluorine, and sodium. Typical amounts of these in this LiOH monohydrate are as follows: Ca: 100wtppm~1.29wt% F: 0.1~1.29wt% Na: 0.1~1.29% by weight.

[0113] Furthermore, depending on the composition of the PM, significant amounts of zinc, aluminum, potassium and chlorine may be present. In these cases, the LiOH monohydrate obtained after step (e1) has characteristic amounts in the following ranges: Zn: 20wtppm~1.29wt% Al: 50wtppm~1.29wt% K: 0.1~1.29wt% Cl: 0.1~1.29% by weight.

[0114] Depending on the drying conditions, anhydrous LiOH is obtained instead of the monohydrate, in which the characteristic amounts of the above-mentioned impurities for the monohydrate are highly concentrated by a factor of 1.75 (corresponding to the molar weight of the monohydrate divided by the molar weight of the anhydrous) relative to 100% anhydrous LiOH.

[0115] All applicable steps, including steps (b), (c), (d1) and (e), are preferably carried out in an inert atmosphere, such as nitrogen, argon, or in CO2-free air.

[0116] In one embodiment of the invention, Li is recovered from the solution obtained in step (c) by precipitation as Li carbonate by addition of sodium or ammonium carbonate or, preferably under pressure, by carbonic acid formed by dissolution of carbon dioxide (step e5).

[0117] In one embodiment, this Li carbonate is dissolved again by further adding CO2, preferably under pressure, to the solution to form dissolved LiHCO3 (e6). Possible impurities can be separated using state of the art purification techniques, such as solvent extraction, precipitation and / or ion exchange. After this optional purification, the Li carbonate can be obtained by increasing the temperature of the solution, which directly results in the precipitation of the Li carbonate (e7). Subsequent solid-liquid separation allows the pure Li carbonate to be obtained.

[0118] In a preferred embodiment of the present invention, Li is recovered as LiOH.

[0119] The resulting solid Li salt and / or LiOH may be further purified by dissolution and recrystallization as known in the art.

[0120] The Ni and / or Co containing alloy obtained from step (d) may subsequently be subjected to step (f) in order to extract Ni, and, where applicable, Co, and, where applicable, other valuable metals, such as copper. For the extraction, acid or ammonia leaching may be applied.

[0121] During such step (f), the transition metal material may be treated with a leaching agent, preferably an acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid, or a combination of at least two of the foregoing, such as a combination of nitric acid and hydrochloric acid. - inorganic acids, e.g. sulfuric acid, hydrochloric acid, nitric acid, organic acids, such as methanesulfonic acid, oxalic acid, citric acid, aspartic acid, malic acid, ascorbic acid or glycine, a base, such as ammonia, an amine, an aqueous solution of ammonia, ammonium carbonate, or a mixture of ammonia and carbon dioxide, or - Chelating agents, such as Na4EDTA, Na2H2EDTA, H4EDTA (in the following sections, these three chelating agents are collectively referred to as simply EDTA) or dimethylglyoxime.

[0122] In one form, the leaching agent comprises an aqueous acid, such as an inorganic or organic aqueous acid. In another form, the leaching agent comprises a base, preferably ammonia or an amine. In another form, the leaching agent comprises a complexing agent, preferably a chelating agent. In another form, the leaching agent comprises an inorganic acid, an organic acid, a base or a chelating agent.

[0123] The concentration of the leaching agent may vary within a wide range, for example in the range of 0.1 to 98% by weight, preferably between 10% and 80%. A preferred example of an aqueous acid is aqueous sulfuric acid, for example with a concentration in the range of 10 to 98% by weight. Preferably, the aqueous acid has a pH value in the range of -1 to 2. The amount of acid is adjusted so that an excess of acid with respect to the transition metal is maintained. Preferably, the pH value of the solution obtained at the end of step (f) is in the range of -0.5 to 2.5. A preferred example of a base as leaching agent is aqueous ammonia, preferably with a molar ratio of NH3 to metal (Ni, Co) of 1:1 to 6:1, preferably 2:1 to 4:1, in the presence of also carbonate or sulfate ions. Suitable chelating agents such as EDTA or dimethylglyoxime are often applied in a molar ratio of 1:1 to 3:1.

[0124] The leaching may be carried out in the presence of an oxidizing agent. A preferred oxidizing agent is oxygen, either as a pure gas or in a mixture with an inert gas, such as nitrogen, or as air. Other oxidizing agents are oxidizing acids, such as nitric acid, or peroxides, such as hydrogen peroxide.

[0125] In one embodiment of the present invention, such step (f) may be carried out by dissolving the solid Ni concentrate obtained in step (c) or (d) in an acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid.

[0126] In one embodiment of the present invention, such step (f) may be carried out by treating the solid Ni concentrate obtained in step (c) or (d) with an aqueous solution of ammonium carbonate or ammonium bicarbonate, which may contain additional ammonia.

[0127] In one embodiment of the present invention, the Ni concentrate obtained from step (c) or (d) is treated in step (f) with an acid selected from sulfuric acid, hydrochloric acid, nitric acid, methanesulfonic acid, oxalic acid and citric acid, or a combination of at least two of the above, for example a combination of nitric acid and hydrochloric acid. In the case of aqueous acids, the concentration of the acid may vary within a wide range, for example in the range between 0.1 and 99% by weight, preferably between 10% and 96%. The amount of acid is adjusted so that an excess of acid is maintained. Preferably, the pH value of the solution obtained at the end of step (f) is in the range of -0.5 to 2.

[0128] A preferred example of an aqueous acid is an aqueous sulfuric acid solution, for example having a concentration in the range of 10 to 98% by weight.

[0129] The treatment according to step (f) may be carried out at a temperature in the range of from 20 to 200° C., in particular from 20 to 130° C. If a temperature above 100° C. is desired, step (f) is carried out at a pressure above 1 bar. Otherwise, normal pressure is preferred.

[0130] In one embodiment of the present invention, step (f) is carried out in a container protected against strong acids, such as molybdenum and copper-rich steel alloys, nickel-based alloys, duplex stainless steel, or glass-lined or enamel- or titanium-coated steel. Further examples are polymer linings and containers made of acid-resistant polymers, such as polyethylene, e.g., HDPE and UHMPE, fluorinated polyethylene, perfluoroalkoxyalkanes ("PFA"), polytetrafluoroethylene ("PTFE"), PVDF, and FEP. FEP stands for fluorinated ethylene propylene polymer, i.e., a copolymer of tetrafluoroethylene and hexafluoropropylene.

[0131] The slurry resulting from step (f) may be stirred or agitated or subjected to a grinding process, for example in a ball mill or stirred ball mill, which often provides better access for the water or acid to the particulate transition metal material.

[0132] In one embodiment of the present invention, step (f) has a duration in the range of 10 minutes to 10 hours, preferably 1 to 3 hours. For example, the reaction mixture in step (f) is stirred or pumped at a power of at least 0.1 W / l to achieve good mixing and to avoid settling of insoluble components. Shearing can be further improved by utilizing baffles. All these shearing devices must be applied with sufficient corrosion resistance and may be manufactured from similar materials and coatings as those described for the vessel itself.

[0133] Step (f) may be carried out under an atmosphere of air or air diluted with N. However, it is preferred to carry out step (f) under an inert atmosphere, such as nitrogen or a noble gas, such as Ar.

[0134] Treatment according to step (f) dissolves metal compounds, including impurities other than carbon and organic polymers, remaining after leaching of LiOH in step (b). In most embodiments, a slurry is obtained after performing step (f). Residual lithium and transition metals, such as but not limited to nickel, cobalt, copper, and, where applicable, manganese, are often in dissolved form, e.g., in the form of salts, in the leachate.

[0135] In embodiments where a so-called oxidizing acid is used in step (f), it is preferred to add a reducing agent to remove unused oxidants. Examples of oxidizing acids are nitric acid and a combination of nitric acid and hydrochloric acid. In the context of the present invention, hydrochloric acid, sulfuric acid and methanesulfonic acid are preferred examples of non-oxidizing acids.

[0136] In one embodiment, step (f) is carried out under an inert gas, such as nitrogen or argon.

[0137] Depending on the concentration and amount of aqueous acid used in step (f), the liquid phase obtained in step (f) may have a transition metal concentration in the range of 1 up to 25% by weight, preferably 6-15% by weight. The transition metal concentration depends on the solubility of the salts corresponding to the acid employed. Preferably, to ensure a high metal concentration in solution, step (f) is carried out such that the transition metal concentrations of the main metals, e.g. Ni and possibly Co and Mn, are just below the solubility limit of the least soluble salt.

[0138] By dissolving the Ni concentrate in step (f) in the subsequent step (f1), the pH value of the above slurry or solution can be adjusted to 2.5-8, preferably 5.5-7.5, even more preferably 6-7. The pH value can be determined by conventional means, such as potentiometric titration, which refers to the pH value of the continuous liquid phase at 20° C. The adjustment of the pH value is done by dilution with water or by addition of a base, or by a combination of these. Examples of suitable bases are ammonia and alkali metal hydroxides, such as LiOH, NaOH or KOH in solid form, for example as pellets, or preferably as an aqueous solution. Combinations of at least two of the foregoing are also possible, such as ammonia and aqueous caustic soda.

[0139] Preferably, optional step (f2) comprises removing the residual precipitate of carbonates, oxides, phosphates, hydroxides or oxyhydroxides of Al, Cu, Fe, Zr, Zn, or a combination of at least two of the above, formed in optional step (f1). The precipitate may be formed during the adjustment of the pH value. The phosphate may be stoichiometric or basic phosphate. Without wishing to be bound by any theory, the phosphate may occur in the case of phosphate formation through hydrolysis of hexafluorophosphoric acid or its decomposition products formed during the pretreatment of the particulate material provided in this step (a). The precipitate may be removed by filtration, or by centrifugation, or by sedimentation. Preferred filters are belt filters, filter presses, suction filters and cross-flow filters. Filter aids and / or flocculants may be added to improve solid-liquid separation.

[0140] In a preferred embodiment of the present invention, step (f2) optionally comprises step (f3), which comprises treating the solution obtained after step (f1) or step (f2) with metallic nickel, metallic cobalt or metallic manganese, or any combination of at least two of the foregoing.

[0141] In optional step (f3), the solution obtained after step (f2) is contacted with metallic nickel, cobalt or manganese, or a combination of at least two of the foregoing, for example in a column. In such an embodiment, it is advantageous to provide a column packed with metallic nickel, cobalt or manganese, or a combination of at least two of the foregoing, in agglomerates or granules, for example as a fixed bed, and to allow the solution stream to flow through such column.

[0142] In one embodiment of the present invention, step (f3) is carried out at normal pressure.

[0143] In one embodiment of the invention, step (f3) has a duration ranging from 30 minutes to 5 hours, the duration corresponding to the average residence time if step (f3) is carried out in a column.

[0144] In one embodiment of the present invention, step (f3) is carried out at a pH value ranging from 1 to 6, preferably at a pH of from 2 to 5. The lower the pH value in step (f3), the more metals selected from Ni, Co and Mn dissolve under hydrogen formation.

[0145] Step (f3) is particularly useful for removing traces of copper. By carrying out step (f3), no new impurities are introduced into the solution of transition metals that would require additional purification steps. Even if the metallic nickel, cobalt or manganese contains traces of copper, these will not dissolve.

[0146] The separation of copper in step (f3) may be carried out by electrolysis, preferably using an electrochemical filter cell, using a conductive particulate material, such as graphite contained in the black agglomerates, as an electrode.

[0147] Alternatively, copper may be extracted by solvent extraction or ion exchange prior to precipitation of Al, Fe, Zr and / or Zn and recovered as high grade copper by electrowinning.

[0148] The individual metals may be recovered as pure metal salts from the mixed Ni-, Co- and / or Mn-containing solutions by procedures known in the art, such as precipitation as oxides, hydroxides, carbonates or sulfides, solvent extraction, ion exchange, electrowinning, etc. These pure metal salts may be reintroduced into the synthesis of the active cathode material, for example, by steps (g1) and (g) below.

[0149] Optional step (g) is typically carried out following step (f) and optional steps (f1), (f2), (f3) and comprises precipitating the transition metals as mixed hydroxides or mixed carbonates, preferably as mixed hydroxides.

[0150] In a preferred embodiment of the present invention, step (g) is carried out by adding ammonia or an organic amine, such as dimethylamine or diethylamine, preferably ammonia, and at least one inorganic base, such as lithium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate or potassium bicarbonate, or a combination of at least two of the foregoing. It is preferred to add ammonia and sodium hydroxide.

[0151] In one embodiment of the present invention, step (g) is carried out at a temperature in the range of 10-85°C, preferably 20-50°C. In one embodiment of the present invention, the concentration of the organic amine (or ammonia) is in the range of 0.05-1 mol / l, preferably 0.1-0.7 mol / l. The term "ammonia concentration" in this context includes the concentrations of ammonia and ammonium. The Ni in the mother liquor 2+ and Co 2+ Particularly preferred is an amount of ammonia that results in a solubility of each of 1000 ppm or less, more preferably 500 ppm or less.

[0152] In one embodiment of the present invention, mixing is effected during step (g) of the method of the present invention, for example by a stirrer, rotor-stator mixer or ball mill. It is preferred to introduce a stirrer power of at least 1 W / l, preferably at least 3 W / l, more preferably at least 5 W / l, into the reaction mixture. In one embodiment of the present invention, a stirrer power of up to 25 W / l can be introduced into the reaction mixture.

[0153] Optional step (g) of the method of the present invention may be carried out in the presence or absence of one or more reducing agents. Examples of suitable reducing agents are hydrazine, primary alcohols, such as but not limited to methanol or ethanol, as well as ascorbic acid, glucose and alkali metal sulfites. It is preferred not to use any reducing agent in step (g). The use of a reducing agent or an inert atmosphere, or a combination of both, is preferred when a large amount of manganese, for example at least 3 mol % with respect to the transition metal portion of the respective cathode active material, is present in the transition metal oxide material.

[0154] Step (g) of the method of the invention may be carried out under an atmosphere of an inert gas such as, for example, nitrogen or argon or carbon dioxide.

[0155] In one embodiment of the present invention, step (g) is carried out at a pH value in the range of 9 to 13.5, preferably 11 to 12.5, for hydroxides and at a pH value in the range of 7.5 to 8.5, for carbonates. The pH values ​​refer to the pH values ​​in the mother liquor, determined at 23° C.

[0156] Step (g) may be carried out in a batch reactor or (preferably) continuously, for example in a continuous stirred tank reactor, or in a cascade of two or more, for example two or three, continuous stirred tank reactors.

[0157] Step (g) of the method of the present invention can be carried out under air, under an inert gas atmosphere, such as a noble gas or nitrogen atmosphere, or under a reducing atmosphere. An example of a reducing gas is, for example, SO2. It is preferable to operate under an inert gas atmosphere, especially nitrogen gas.

[0158] For purposes of further purification, the solid recovered in step (g) may be separated and dissolved in an acid, such as hydrochloric acid, or more preferably, sulfuric acid.

[0159] By carrying out the method of the present invention, the transition metals nickel and / or cobalt, and other metals, if applicable, can be recovered from the nickel- and / or cobalt-containing cathode material in a form that can be very easily converted into an active cathode material. In particular, the method of the present invention allows the recovery of transition metals, such as nickel, and optionally cobalt and / or manganese, containing only tolerably trace amounts of impurities, such as copper, iron and zinc, for example less than 10 ppm copper, preferably even less, for example 1 to 5 ppm.

[0160] In one embodiment of the present invention, in an additional step (g1) before step (g), nickel, cobalt and / or manganese salts are added to the recycled metal salt solution from step (f) or (f1), (f2) or (f3) to adjust the metal ratio to the desired mixed metal hydroxide precipitate composition, which can be used as a precursor material for the production of the cathode active material. During such precipitation, additional metal salts may be added, preferably as an aqueous solution of the anion of the acid used in step (f), an example of such a metal is aluminum, which can be added as aluminum sulfate. The mixed metal hydroxide precipitate can be separated from the liquid by solid-liquid separation and dried to obtain a dry mixed metal hydroxide precipitate having a water content of 10% by weight or less. This allows the cathode active material precursor to be directly obtained in the continuous precipitation step (g).

[0161] In one embodiment of the present invention, the solid alloy containing Ni and / or Co obtained in step (d), preferably after atomization, is treated with ammonium (bi)carbonate in aqueous solution at a concentration of 0.2-30% by weight, preferably 1-20% by weight. The slurry may be heated to a temperature of 30-150° C. Above the boiling point of the mixture, the heating is carried out under pressure. Below the boiling point, the application of pressure is advantageous in order to maintain sufficient ammonia and carbon dioxide in the system.

[0162] The treatment with ammonium (bi)carbonate may be carried out under an inert atmosphere or in the presence of oxygen, e.g. under air. The leachate or solution may also contain additional ammonia and / or hydrogen peroxide.

[0163] The ammonium (bi)carbonate treatment dissolves Ni and / or Co, and where applicable Cu, as ammonium complexes. The concentration of the metal ammonium complexes in the leach liquid may be in the range of 0.2-30 wt% by metal, preferably 1-15 wt% by metal. The solution obtained by this treatment is subjected to solid-liquid separation, resulting in a solution containing mainly ammonium complexes of Ni, and where applicable Co and Cu, and a separated solid residue containing mainly other transition metals, i.e. Mn and Fe, where applicable.

[0164] The resulting solution can be heated and the ammonia removed by purging with carbon dioxide. This results in first the Ni carbonate and, in longer treatments, advantageously at higher temperatures, also the Co carbonate as precipitates. This allows both metals to be separated. In one embodiment of the invention, the Ni and Co carbonates are not separated from each other. The precipitated mixed Ni / Co carbonate is separated from the mother liquor and dissolved in sulfuric acid or another acid to obtain a solution of the corresponding Ni salt and, if applicable, Co salt. This solution may also contain small amounts of Cu salts, which can be removed by treatment with the metals Ni, Co or Mn as described above. Other impurities such as Fe or Al, which may be present in low concentrations, can be removed by hydroxide or carbonate precipitation at pH values ​​of 2.5 to 8, also as described above.

[0165] Ni hydroxide and Co hydroxide can be co-precipitated from the purified Ni salt and / or Co salt solution.

[0166] In one embodiment of the present invention, the solution is further processed to extract the Ni and Co salts separately, for example, by solution extraction. The pure metals can be recovered from the separated Ni and Co salts via electrochemical methods known in the art.

[0167] In one embodiment, the precipitation of the transition metals after steps (f1), (f2) and (f3) is carried out with hydrogen at elevated pressure. For this, the pH value of the solution is kept basic by the addition of ammonia and / or ammonium carbonate. This allows Ni, Co and Cu to be precipitated as metals. Certain catalysts known in the art may be added to improve this reaction. EXAMPLES

[0168] Description of method Particle size distribution measurements, including determination of D50, are performed according to ISO 13320 EN:2009-10.

[0169] Elemental analysis of lithium, calcium and manganese (performed to determine, inter alia, the Li, Ca, Mn content of the particulate material provided in step (a)); The reagents are Deionized water, hydrochloric acid (36%), K2CO3-Na2CO3 mixture (dry), Na2B4O7 (dry), hydrochloric acid 50% by volume (1:1 mixture of deionized water and hydrochloric acid (36%)). All reagents are PA grade.

[0170] Sample preparation 0.2-0.25 g of particulate material for this step (a) (typically obtained from waste lithium ion batteries after carrying out the pre-reduction step (i)) is weighed into a Pt crucible and K2CO3-Na2CO3 / Na2B4O7 melt digestion is applied. The sample is burned in an unshielded flame and subsequently completely ashed at 600 °C in a muffle furnace. The remaining ash is mixed with K2CO3-Na2CO3 / Na2B4O7 (0.8 g / 0.2 g) and melted until a transparent melt is obtained. The cooled molten cake is dissolved in 30 mL of water and 12 mL of 50% by volume hydrochloric acid is added. The solution is filled up to the specified volume of 100 mL. This work up is repeated three times independently and in addition a blank sample is prepared for reference purposes.

[0171] measurement The Li, Ca and Mn in the resulting solution are determined by inductively coupled plasma optical emission spectroscopy (ICP-OES). Instrument: ICP-OES Agilent 5100 SVDV; Wavelengths: Li 670.783 nm; Ca 396.847 nm; Mn 257.610 nm; Internal standard: Sc 361.383 nm; Dilution factors: Li 100, Ca 10, Mn 100; Calibration: external.

[0172] Elemental analysis of fluorine and fluorides is carried out according to the following standardized methods: DIN EN 14582:2016-12 for sample preparation for determination of total fluorine content (waste samples); detection method is ion-selective electrode measurement; DIN 38405-D4-2:1985-07 (water samples; digestion of inorganic solids followed by acid-supported distillation and fluoride determination using an ion-selective electrode).

[0173] Other metal impurities and phosphorus are similarly determined by elemental analysis using ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy) or ICP-MS (Inductively Coupled Plasma Mass Spectroscopy). Total carbon is determined by a thermal conductivity detector after combustion.

[0174] The phase composition of the solid (including the identity of manganese(II) oxide, and Ni and Co (typically metallic) in oxidation states lower than +2 in the particulate material provided in step (a)) is determined by powder x-ray diffraction (PXRD), which is carried out as follows.

[0175] The sample is ground to a fine powder and packed into the sample holder.

[0176] It utilizes two devices, each with its own separate radiation source.

[0177] (1) Measurements applying Cu radiation: The equipment used is a Bruker D8 Advance Series 2 with an autosampling unit. Primary side: Cu anode, beam divergence angle aperture 0.1° with ASS; Secondary side: divergent beam aperture 8mm, Ni 0.5mm, Solar 4°, Lynx-Eye (3° aperture).

[0178] (2) Measurements applying Mo radiation: The equipment used is a Bruker D8 Discover A25 with an autosampling unit. Primary: Mo anode with Johansson monochromator (Mo-K-Alpha 1), axial solar 2.5°; Secondary: ASS, solar 2.5°, Lynx-Eye XE detector (3.77° aperture).

[0179] References are used to identify matches with the obtained reflection pattern. All relevant phases are well known in the literature, and the following references are consulted and used to calculate the theoretical diffraction pattern (see position and intensity of reflections in Table 1 below): a) Co x Ni 1-x : space group Fm-3m; x=0.5: Taylor et al., J. Inst. Met. (1950) 77, 585-594. x=0: Buschow et al.; J. Magn. Magn. Mater. 1983, 38, 1-22. b) Co; space group P63 / mmc; Buschow et al.; J. Magn. Magn. Mater. 1983, 38, 1-22. c) Li2CO3, space group C2 / c; J. Alloys Compd. (2011), 509, 7915-7921 d) LiAlO2, space group R-3m; Marezio et al., J. Chem. Phys. (1966) 44, 3143-3145. e) MnO, space group Fm-3m, Locmelis et al., Z. Anorg. Allg. Chem. 1999, 625, 1573.

[0180] [Table 1]

[0181] If characteristic reflections overlap with those of different crystalline phases (especially graphite, which constitutes the largest proportion of the sample), additional measurements are performed utilizing alternative radiation sources (e.g. Mo K alpha instead of Cu K alpha).

[0182] Abbreviations In the context of the present invention, normal pressure means 1 atm or 1013 mbar. "Normal conditions" means normal pressure and 20° C. Nl stands for normal liter, i.e. liter at normal conditions (1 atm, 20° C.). PFA stands for perfluoroalkoxy polymer.

[0183] Percentages refer to % by weight unless specifically defined otherwise. The expressions % by weight and wt% may be used interchangeably. Whenever mentioned, the terms "room temperature" and "ambient temperature" refer to a temperature between about 18° C. and 25° C. XRD refers to powder x-ray examination (radiation as indicated, typically Cu k-alpha 1 radiation at 154 pm or Mo k-alpha 1 radiation at 71 pm).

[0184] The present invention is further illustrated by the following examples.

[0185] [Example 1] Preparation of reduced mass from waste lithium-ion batteries A quantity of about 1 ton of mechanically processed battery scrap containing spent positive active material, containing nickel, cobalt and manganese, organic carbon in the form of graphite and soot, as well as residual electrolyte and further impurities including fluorine compounds, phosphorus and calcium among others, is treated to obtain reduced mass by the method described in Jia Li et al., Journal of Hazardous Materials 302 (2016) 97-104. The atmosphere in the roasting system is air, where oxygen reacts with the carbon in the battery scrap to form carbon monoxide, and the treatment temperature is 800°C.

[0186] After reacting and cooling to ambient temperature, the heat treated material is recovered from the furnace and mechanically processed to obtain particulate material that is analyzed by X-ray powder diffraction (Figures 1 and 2: Mo Ka radiation, Figures 3 and 4: Cu Ka radiation), elemental analysis (Table 2) and particle size distribution (Table 3).

[0187] The lithium content is 3.6% by weight and serves as a reference for all further leaching examples (see below). The fluorine is mainly expressed as inorganic fluoride (88%). The particle size is well below 1 mm, with a D50 determined to be 17.36 μm.

[0188] Comparing the obtained XRD pattern with the calculated reference patterns of Ni (CoxNi1-x, which is identical to the pattern for x=0-0.6), Co, Li2CO3 and LiAlO2 (see reference patterns in Table 1), it can be concluded that Ni is present exclusively as metallic phase, either as pure Ni or as an alloy in combination with Co. For clarity, this result is confirmed by applying two different radiation sources. The presence of metallic nickel is supported by the qualitative observation that the whole sample, when contacted with a permanent magnetic material, shows a typical ferromagnetic behavior. As lithium salts, Li2CO3 and LiAlO2 are unambiguously identified by their characteristic diffraction patterns.

[0189] The composition of the obtained black powder (PM) is shown in Table 2.

[0190] [Table 2]

[0191] [Table 3]

[0192] [Example 2] Leaching with Ca(OH)2 A quantity of 5 g of the above-mentioned reduced battery scrap material (obtained as shown in Example 1) is loaded into a PFA flask and mixed with 5, 1.5, 1.0 and 0.5 g of solid Ca(OH)2, respectively. 200 g of water is added under stirring and the whole mixture is refluxed for 4 hours.

[0193] After 4 hours, the solids are filtered off and a filtrate sample is taken and analyzed for Li, F, Carbonate, OH and Ca. The results are summarized in Table 4 below.

[0194] [Table 4]

[0195] [Example 2a] Leaching with Ca(OH)2, adding solid to liquid Example 2 is repeated, except that 5 g of the black powder obtained as shown in Example 1 and the specified amount of solid Ca(OH)2 are added simultaneously to 200 g of water under stirring. The results are similar to those reported in Table 4.

[0196] [Example 3] More solids Particulate material (PM) as described in Example 1 in amounts of 10, 20 and 30 g is respectively loaded into a PFA flask and mixed with solid Ca(OH)2 at a fixed weight ratio of PM:Ca(OH)2=3.3:1. Each sample is further treated by adding 200 g water following Example 2, except that it is refluxed for 6 hours. The results are shown in Table 5.

[0197] Based on these results, we conclude that the efficiency of the present leaching process is not affected by the PM solids content.

[0198] [Table 5]

[0199] [Example 4] Parameter Variation Following the procedure of Example 2a, solid Ca(OH)2 and particulate material (PM) as described in Example 1 are added to 836.8 g of preheated water in a baffled glass reactor with stirring (three-stage cross-beam stirrer, 60 mm diameter). After continued stirring at constant temperature for the period (t) indicated in Table 6, the solids are filtered off and a filtrate sample is analyzed. The amount of Ca(OH)2 and PM, temperature, stirring parameters, and analytical results (%=g found in 100 g filtrate) are also summarized in Table 6.

[0200] [Table 6]

[0201] [Example 5] Solid LiOH from leached lithium filtrate The filtrate obtained from the process according to Example 2 is further treated by step (e1) above to obtain solid LiOH as monohydrate: 1 L of the filtrate containing 0.21 wt. % lithium is concentrated by evaporation (40° C., 42 mbar) and finally dried at 40° C. and constant flow of nitrogen for 24 hours. FIG. 5 shows the obtained LiOH monohydrate containing traces of the impurity Li2CO3, due to contact with air during almost all process steps. Elemental analysis reveals carbonaceous impurities followed by F, Na, Ca, K as main impurities (>200 ppm) and Al and Zn as trace impurities (<200 ppm).

[0202] [Example 6] Laboratory scale refining The finely divided mass (black powder) described in Example 1 is leached for 6 hours according to Example 4. The leaching residue obtained after filtration contains, by dry weight, approximately 2.2% total fluorine, 26.3% carbon, 13.9% calcium, 8% cobalt, 2.9% copper, 0.2% lithium, 4.9% manganese, 4.8% nickel and 0.3% phosphorus. 4.23 kg of this material are slurried in water and additivated with 0.63 kg fine quartz sand (d50 approximately 80 μm), 0.01 kg calcium oxide and 0.51 kg molasses. The slurry is filtered and extruded in an extrusion press into 6 mm strands. The strands are dried, calcined at 700° C. and broken into pieces less than 1 cm long. This material is fed to a smelting experiment in a laboratory scale electric arc furnace.

[0203] A graphite crucible with an inner diameter of 180 mm and a height of 210 mm, the inner wall surface (except the bottom) of which is covered with alumina paper with a thickness of 5 mm and lined with chrome corundum casting (87.5% Al2O3, 10.5% Cr2O3, 2% CaO) with a thickness of 30 mm, previously dried at 120°C for 18 hours and then fired at 515°C for 18 hours, is placed in a laboratory-scale electric arc furnace, embedded with graphite felt and sealed on top with refractory mortar. Coke is then charged into the crucible and preheated by an open electric arc at 35 V, 100 A from a top electrode with a diameter of 50 mm until the bottom and surrounding side walls of the oven are red-hot (approximately 950°C). The coke is then discharged by tilting the oven. 516 g of carbon-saturated cast iron, which serves as a counter electrode for the electric arc, is then loaded into the oven together with 250 g of the feed material. After about 10 minutes the material is melted and the remainder of the feed material is added to the furnace in 100g portions with 2 minutes between each addition. The power is increased to 11 kW (50V, 225A). After the addition is complete the temperature in the oven is approximately 1600°C. The power is reduced to 9 kW (60V, 150A) and the melt is kept for 10 minutes. The power is then switched off and the oven is allowed to cool to ambient temperature overnight. The cooled crucible is removed from the oven and crushed. At the bottom of the crucible is about 1 kg of alloy containing mainly nickel, cobalt and copper from battery scrap material as well as iron.

[0204] The components of the alloy are separated by methods known in the art. The present invention includes the following aspects. [Section 1] 1. A method for recovering one or more transition metals and lithium as Li salts from a material that typically comprises waste lithium ion batteries or parts thereof, comprising the steps of: (a) providing a particulate material containing a transition metal compound and / or a transition metal, the transition metal being selected from the group consisting of Ni and Co, at least a portion of the Ni and / or Co being in an oxidation state lower than +2, the particulate material further comprising a lithium salt; (b) treating the material provided in step (a) with a polar solvent, typically a protic solvent; (c) separating the solid residue containing the transition metal from the liquid, optionally followed by subjecting said solid residue to solid-solid separation to recover the transition metal, e.g. Ni; (d) treating the transition metal-containing solid in a smelting furnace to obtain a metal melt containing Ni and / or Co; With the proviso that when the solid residue separated in step (c) is subjected to said solid-solid separation to recover the transition metal, such as Ni, prior to carrying out step (d), the polar solvent used in step (b) contains an alkaline earth hydroxide. [Section 2] Item 1. The method according to item 1, wherein the particulate material provided in step (a) is obtained from used lithium ion batteries, in particular cell materials thereof, and / or scrap materials obtained from the production of lithium ion batteries, or lithium ion positive active materials, and is provided in the form of a dry powder, a wet powder, or a suspension of particles in a liquid. [Section 3] Item 3. The method according to item 1 or 2, wherein the particulate material provided in step (a) comprises particles having an average particle diameter D50 in the range of 1 μm to 2 mm, as measured according to ISO 13320 EN:2009-10. [Section 4] The method according to any one of paragraphs 1 to 3, wherein the transition metal compound and / or transition metals Ni and / or Co in an oxidation state lower than +2 contained in the particulate material prepared in step (a) comprise Ni and / or Co in the metallic state, and the transition metal compound and / or transition metal contained in the particulate material prepared in step (a) are preferably present in an amount detectable by powder x-ray diffraction (Cu-k-alpha-1 radiation). [Section 5] 5. The method according to any one of claims 1 to 4, wherein the lithium salt contained in the particulate material prepared in step (a) comprises one or more of the following salts: LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, and lithium phosphate; or a mixed oxide of Li and one or more of Ni, Co, Mn, Fe, Al, and Cu. [Section 6] Step (b) is carried out in the presence of an alkaline earth hydroxide, preferably i) adding simultaneously to a polar solvent, which is a protic solvent, preferably an aqueous liquid, an alkaline earth hydroxide and / or an alkali oxide, as a solid, or a mixture comprising an alkaline earth hydroxide, as a suspension or solution in a protic solvent, typically an aqueous liquid, and the particulate material provided in step (a); By or ii) adding the particulate material provided in step (a) to a polar solvent, preferably a protic solvent, preferably an aqueous liquid, e.g. water, to obtain a suspension, followed by addition of an alkaline earth hydroxide and / or an alkali oxide as a solid, or a mixture comprising an alkaline earth hydroxide as a suspension or solution in a protic solvent, e.g. an aqueous liquid. By or iii) adding an alkaline earth hydroxide and / or alkali oxide, either as a solid or as a suspension of the solid in a polar solvent, to an aqueous liquid, e.g. water, to obtain a mixture comprising the alkaline earth hydroxide, typically as a suspension or solution in the aqueous liquid, and subsequently combining said mixture with the particulate material provided in step (a); By or iv) adding alkaline earth hydroxide and / or alkali oxide as a solid to the particulate material provided in step (a) to obtain a mixture of solids, followed by addition of a polar solvent, which is a protic solvent, preferably an aqueous liquid, e.g. water. By or v) adding the particulate material provided in step (a) to a polar solvent, preferably an aqueous liquid, such as water, to obtain a suspension, followed by filtering to obtain a filtrate, and subsequently adding to the filtrate an alkaline earth hydroxide and / or an alkali oxide as a solid, or a mixture comprising an alkaline earth hydroxide, typically as a suspension or solution in a polar solvent, preferably an aqueous liquid. The method according to any one of items 1 to 5, wherein the method is carried out by [Section 7] 7. The method according to any one of the preceding claims, wherein the polar solvent in step (b) contains calcium hydroxide, which is added to the polar solvent as such or is formed in situ upon contact of calcium oxide with a polar solvent selected from a protic solvent, such as an aqueous liquid or water. [Section 8] 8. The method according to any one of items 1 to 7, wherein the particulate material provided in step (a) comprises material obtained from waste lithium ion batteries after a preliminary step (i) of heating to a temperature in the range of 80 to 900 ° C, in particular 200 to 800 ° C, under inert or reducing conditions, the preliminary step (i) typically being carried out after discharging, dismantling and / or crushing the lithium ion batteries. [Section 9] 9. The method of claim 8, wherein the heating step (i) is carried out under reducing conditions comprising the presence of carbon and / or a reducing gas selected from hydrogen and carbon monoxide. [Section 10] Item 10. The method according to item 8 or 9, wherein in the preliminary step (i), the heating temperature is within a range of 350 to 500° C., particularly 350 to 450° C., and step (i) is carried out in the presence of 35% or more by volume of hydrogen; or in the preliminary step (i), the heating temperature is within a range of 500 to 850° C., particularly 600 to 800° C., and step (i) is carried out in the presence of carbon in an atmosphere containing up to 20% by volume of oxygen. [Section 11] 11. The method according to any one of paragraphs 1 to 10, wherein the particulate material provided in step (a) is obtained from a lithium ion battery after mechanical removal of the casing, wiring or circuitry and discharging, and the material is not exposed to a temperature of 400° C. or higher under oxidizing conditions prior to subjecting the material to step (a). [Section 12] Item 12. The method according to any one of items 1 to 11, comprising the additional step of subjecting the solid obtained in step (c) to solid-solid separation, for example magnetic separation. [Section 13] 13. The process according to any one of paragraphs 1 to 12, wherein the transition metal-containing solid is dried to a residual liquid content of less than 5 wt.%, preferably less than 1 wt.%, and / or pelletized before being introduced into step (d). [Section 14] 14. The method of any one of paragraphs 1 to 13, wherein in step (d), the temperature in the furnace at the point of collection is between 1200° C. and 1600° C., and the furnace is operated in continuous or batch mode. [Section 15] 15. The method of any one of the preceding claims, wherein the solid treated in step (d) further contains one or more of the elements copper, iron and manganese. [Section 16] 12. The process according to any one of the preceding claims, comprising the additional step of recovering lithium as lithium hydroxide from the liquid obtained in step (c) by crystallization or as lithium carbonate after adding carbon dioxide to the liquid obtained in step (c) and isolating the lithium carbonate formed. [Section 17] Item 16. A solid alloy obtained upon cooling the melt obtained in step (d) of the method according to any one of items 1 to 15.

Claims

1. 1. A method for recovering one or more transition metals and lithium as Li salts from a material comprising waste lithium ion batteries or parts thereof, comprising: (a) providing a particulate material containing a transition metal compound and / or a transition metal, the transition metal being selected from the group consisting of Ni and Co, at least a portion of the Ni and / or Co being in an oxidation state lower than +2, the particulate material further comprising a lithium salt; (b) treating the material provided in step (a) with a polar solvent; (c) separating the solid residue containing the transition metal from the liquid; and (d) treating the transition metal-containing solid in a smelting furnace to obtain a metal melt containing Ni and / or Co; The process according to claim 1, wherein the polar solvent used in step (b) contains an alkaline earth hydroxide, and the treatment with the alkaline earth hydroxide is carried out at a temperature in the range of 70 to 150° C. for a period of 1 to 24 hours.

2. 2. The method of claim 1, wherein the particulate material provided in step (a) is obtained from used lithium ion batteries, and / or scrap material obtained from the production of lithium ion batteries, or lithium ion positive electrode active material, and is provided in the form of a dry powder, a wet powder, or a suspension of particles in a liquid.

3. 3. The method of claim 1 or 2, wherein the particulate material provided in step (a) comprises particles having a mean particle diameter D50 in the range of 1 μm to 2 mm, as detected according to ISO 13320 EN:2009-10.

4. 4. A method according to any one of claims 1 to 3, wherein the transition metal compounds and / or transition metals Ni and / or Co in an oxidation state lower than +2 contained in the particulate material prepared in step (a) comprise Ni and / or Co in the metallic state, and the transition metal compounds and / or transition metals contained in the particulate material prepared in step (a) are present in an amount detectable by powder x-ray diffraction (Cu-k-alpha-1 radiation).

5. 5. A method according to any one of claims 1 to 4, wherein the particulate material provided in step (a) contains lithium salts comprising one or more of the following salts: LiOH, LiF, Li2O, Li2CO3, LiHCO3, lithium aluminate, lithium phosphate; mixed oxides of Li and one or more of Ni, Co, Mn, Fe, Al, Cu.

6. step (b) is carried out in the presence of an alkaline earth hydroxide; i) adding simultaneously to a polar solvent, which is a protic solvent, a mixture comprising an alkaline earth hydroxide and / or an alkali oxide as a solid, or an alkaline earth hydroxide as a suspension or solution in a protic solvent, and the particulate material provided in step (a); By or ii) adding the particulate material provided in step (a) to a polar solvent, which is a protic solvent, to obtain a suspension, followed by adding an alkaline earth hydroxide and / or an alkali oxide as a solid, or a mixture comprising an alkaline earth hydroxide as a suspension or solution in the protic solvent. By or iii) adding an alkaline earth hydroxide and / or an alkali oxide, either as a solid or as a suspension of the solid in a polar solvent, to the aqueous liquid to obtain a mixture comprising alkaline earth hydroxide, and subsequently combining said mixture with the particulate material provided in step (a); By or iv) adding an alkaline earth hydroxide and / or an alkali oxide, as a solid, to the particulate material provided in step (a) to obtain a mixture of solids, followed by adding a polar solvent, which is a protic solvent. By or v) adding the particulate material prepared in step (a) to a polar solvent, which is a protic solvent, to obtain a suspension, followed by filtering to obtain a filtrate, and then adding, as a solid, an alkaline earth hydroxide and / or an alkali oxide, or a mixture containing an alkaline earth hydroxide, to the filtrate. The method according to any one of claims 1 to 5, wherein the method is carried out by

7. 7. A method according to any one of claims 1 to 6, wherein the polar solvent in step (b) contains calcium hydroxide, which is added to the polar solvent as such or which is formed in situ upon contact of calcium oxide with a polar solvent selected from protic solvents.

8. 8. The method according to any one of claims 1 to 7, wherein the particulate material provided in step (a) comprises material obtained from waste lithium ion batteries after a preliminary step (i) of heating to a temperature in the range of 80-900°C under inert or reducing conditions, the preliminary step (i) being carried out after discharging, dismantling and / or crushing the lithium ion batteries.

9. 9. The method of claim 8, wherein the heating step (i) is carried out under reducing conditions comprising the presence of carbon and / or a reducing gas selected from hydrogen and carbon monoxide.

10. 10. The method according to claim 8 or 9, wherein in the preliminary step (i), the heating temperature is in the range of 350-500°C and step (i) is carried out in the presence of at least 35% by volume of hydrogen, or wherein in the preliminary step (i), the heating temperature is in the range of 500-850°C and step (i) is carried out in the presence of carbon in an atmosphere containing up to 20% by volume of oxygen.

11. 11. The method of any one of claims 1 to 10, wherein the particulate material provided in step (a) is obtained from a lithium ion battery after mechanical removal of casing, wiring or circuitry and discharging, and said material has not been exposed to temperatures of 400°C or higher under oxidizing conditions prior to subjecting it to step (a).

12. 12. The process according to any one of claims 1 to 11, comprising the additional step of subjecting the solid obtained in step (c) to solid-solid separation.

13. 13. The process according to any one of claims 1 to 12, wherein the transition metal-containing solid is dried to a residual liquid content of less than 5 wt.% and / or pelletized prior to being introduced into step (d).

14. 14. The method according to any one of claims 1 to 13, wherein in step (d) the temperature in the furnace at the point of collection is between 1200°C and 1600°C, and the furnace is operated in continuous or batch mode.

15. 15. The method of any one of claims 1 to 14, wherein the solid treated in step (d) further contains one or more of the elements copper, iron and manganese.

16. 12. The process according to any one of claims 1 to 11, comprising the additional step of recovering lithium as lithium hydroxide from the liquid obtained in step (c) by crystallization or as lithium carbonate after adding carbon dioxide to the liquid obtained in step (c) and isolating the lithium carbonate formed.

Citation Information

Patent Citations

  • Battery recycling

    EP1589121A1

  • Method for recovering lithium, cobalt and other metal

    JP2012112027A

  • Method for recovering valuable metal

    JP2012224876A

  • Method for separating and recovering valuable material from used lithium ion battery

    JP2012229481A

  • Spherical particles, production and use thereof

    WO2014180743A1